Sheet and method for manufacturing the sheet
By sandwiching a fiber layer with fine fibrous cellulose between two resin layers with controlled surface roughness, the laminated sheet achieves high transparency, addressing the limitations of conventional sheets.
Patent Information
- Application Number
- JP2020214793
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-27
- Filing Date
- 2020-12-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2040-12-24
AI Technical Summary
Conventional laminated sheets with a fiber layer containing fine fibrous cellulose and a resin layer suffer from limited transparency, which is a hindrance for applications requiring high transparency.
A laminated sheet structure is developed where a fiber layer with fibrous cellulose of 1000 nm or less in width is sandwiched between two resin layers, with both sides of the sheet having a surface roughness of 12.0 nm or less, enhancing transparency.
The proposed sheet achieves high transparency, as evidenced by a haze value less than 0.5% and a total light transmittance of 85% or more, making it suitable for optical members and applications requiring high transparency.
Smart Images

Figure 0007665979000007 
Figure 0007665979000008 
Figure 0007665979000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a sheet and a method for producing the sheet. Specifically, the present invention relates to a sheet containing fine fibrous cellulose and a method for producing the sheet. [Background technology]
[0002] In recent years, materials using renewable natural fibers have been attracting attention due to the need to replace petroleum resources and growing environmental awareness. Among natural fibers, fibrous cellulose with a fiber diameter of 10 μm to 50 μm, especially fibrous cellulose (pulp) derived from wood, has been widely used mainly for paper products.
[0003] As fibrous cellulose, fine fibrous cellulose with a fiber diameter of 1 μm or less is also known. In addition, sheets made of such fine fibrous cellulose and composites containing a fine fibrous cellulose-containing sheet and a resin layer have been developed. It is known that in sheets and composites containing fine fibrous cellulose, the number of contact points between fibers increases significantly, and therefore the tensile strength and the like are greatly improved. It is also known that transparency is greatly improved when the fiber width becomes shorter than the wavelength of visible light.
[0004] When forming a composite containing a fine fibrous cellulose-containing sheet and a resin layer, it has been considered to add additives to each layer in order to increase the adhesion between the fine fibrous cellulose-containing sheet and the resin layer. For example, Patent Document 1 considers adding a polycarboxylic acid polymer to the fine fibrous cellulose-containing sheet. Patent Document 2 also proposes heat-sealing a polycarbonate sheet to a fine fibrous cellulose-containing sheet to form a laminate. In this case, a fine fibrous cellulose-containing sheet that has been previously soaked in a primer treatment solution such as an acrylic primer and a polycarbonate sheet are heat-sealed to form a laminate.
[0005] Patent Document 3 proposes that a silane coupling agent is blended into a fine fibrous cellulose-containing sheet to improve the adhesion between the resin layer and the fine fibrous cellulose-containing sheet. Patent Document 4 also considers that, in a laminate having a fine fibrous cellulose-containing fiber layer and a resin layer in contact with one side of the fiber layer, an adhesion aid is blended into the resin layer to improve the adhesion between the fiber layer and the resin layer. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2014-223737 A [Patent Document 2] JP 2010-023275 A [Patent Document 3] International Publication No. WO2011 / 118360 [Patent Document 4] International Publication No. WO2017 / 126432 Summary of the Invention [Problem to be solved by the invention]
[0007] The laminated sheet obtained by laminating a fiber layer containing fine fibrous cellulose and a resin layer has a wide range of applications, and depending on the application, the laminated sheet may be required to have high transparency. However, in the conventional laminated sheet obtained by laminating a fiber layer containing fine fibrous cellulose and a resin layer, there is room for improvement in the transparency of the laminated sheet. Therefore, in order to solve such problems of the conventional technology, the present inventors have conducted research with the aim of providing a laminate sheet having high transparency, which is formed by laminating a fiber layer containing fine fibrous cellulose and a resin layer. [Means for solving the problem]
[0008] As a result of intensive research to solve the above problems, the inventors have found that a sheet having high transparency can be obtained by laminating a resin layer on both sides of a fiber layer containing fibrous cellulose having a fiber width of 1000 nm or less, and further setting the surface roughness (Ra) of both sides of the sheet after laminating each layer to 12.0 nm or less. Specifically, the present invention has the following configuration.
[0009] [1] A sheet having a fiber layer and a resin layer on both sides of the fiber layer, The fiber layer contains fibrous cellulose having a fiber width of 1000 nm or less, A sheet having a surface roughness (Ra) of 12.0 nm or less on both sides of the sheet. [2] The sheet according to [1], wherein the resin layers each have a thickness of 10 μm or less. [3] The sheet according to [1] or [2], wherein the fibrous cellulose has an ionic substituent. [4] The sheet according to [3], wherein the ionic substituent is a phosphorus oxo acid group or a substituent derived from a phosphorus oxo acid group. [5] The sheet according to any one of [1] to [4], wherein the refractive index of the fiber layer is 1.51 to 1.60. [6] The sheet according to any one of [1] to [5], wherein the fiber layer further contains a hydrophilic polymer. [7] The sheet according to [6], wherein the hydrophilic polymer is polyvinyl alcohol. [8] The sheet according to [7], wherein the saponification degree of the polyvinyl alcohol is 99.9% or less. [9] The sheet according to any one of [1] to [8], wherein the resin layer contains an amorphous resin.
[10] The sheet according to any one of [1] to [9], wherein the resin layer is a solvent-coated layer.
[11] The sheet according to any one of [1] to
[10] , wherein the fiber layer has a thickness of 10 to 1000 μm.
[12] The sheet according to any one of [1] to
[11] , wherein the resin layer contains an isocyanate compound.
[13] The sheet according to any one of [1] to
[12] , having a haze value of less than 0.5%.
[14] The sheet according to any one of [1] to
[13] , having a moisture content of 12 mass% or less.
[15] The sheet according to any one of [1] to
[14] , having a tensile modulus of elasticity of 2.5 GPa or more at 23°C and a relative humidity of 50%.
[16] The sheet according to any one of [1] to
[15] , which is for an optical member.
[17] The sheet according to any one of [1] to
[16] , wherein the refractive index ratio between the fiber layer and the resin layer calculated by the following formula is 0.98 or more and 1.02 or less. Refractive index ratio = Refractive index of fiber layer / Refractive index of resin layer
[18] The sheet according to any one of [1] to
[17] , wherein the refractive index of the fiber layer is 1.51 to 1.54.
[19] A method for producing a sheet, comprising a step of forming a resin layer on both sides of a fiber layer containing fibrous cellulose having a fiber width of 1000 nm or less, A method for manufacturing a sheet, wherein the surface roughness (Ra) of both sides of the sheet is 12.0 nm or less.
[20] The method for producing a sheet according to
[19] , wherein the resin layer has a thickness of 10 μm or less.
[21] The step of forming the resin layer is a step of forming a resin layer by applying a resin coating liquid to both sides of the fiber layer, The resin coating liquid contains a solvent. The method for producing a sheet according to
[19] or
[20] , wherein the viscosity of the resin coating liquid is 100 cps or less.
[22] The method for producing a sheet according to
[21] , wherein the solid content in the resin coating liquid is 12 mass % or less. Effect of the Invention
[0010] According to the present invention, it is possible to obtain a sheet having a fiber layer containing fine fibrous cellulose and having high transparency. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view illustrating the structure of the sheet of the present invention. [Diagram 2]FIG. 2 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having phosphorus oxoacid groups and pH. [Diagram 3] FIG. 3 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having a carboxy group and pH. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below. The following description of the components may be based on representative embodiments or specific examples, but the present invention is not limited to such embodiments.
[0013] (Sheet) The present invention relates to a sheet having a fiber layer and a resin layer on both sides of the fiber layer. Here, the fiber layer contains fibrous cellulose having a fiber width of 1000 nm or less, and the surface roughness (Ra) of both sides of the sheet is 12.0 nm or less. In this specification, the fibrous cellulose having a fiber width of 1000 nm or less is sometimes called fine fibrous cellulose or CNF.
[0014] Fig. 1 is a cross-sectional view illustrating the configuration of the sheet of the present invention. As shown in Fig. 1, the sheet 10 of the present invention has a fiber layer 2 containing fine fibrous cellulose, and resin layers 6 containing a resin as a main component on both sides of the fiber layer 2. As shown in Fig. 1, the sheet 10 of the present invention is a sheet having a laminated structure, and is therefore sometimes called a laminated sheet. In the resin layer 6 / fiber layer 2 / resin layer 6 configuration of the sheet 10, the layers are directly laminated in contact with each other.
[0015] The surface roughness (Ra) of both sides of the sheet of the present invention may be 12.0 nm or less, preferably 11.0 nm or less, more preferably 10.0 nm or less, even more preferably 9.0 nm or less, and particularly preferably 8.0 nm or less. The lower limit of the surface roughness (Ra) of both sides of the sheet is not particularly limited, but is preferably, for example, 1.0 nm or more. In the present invention, it is preferable that the surface roughness (Ra) of both sides of the sheet is within the above range. That is, it is preferable that the surface roughness (Ra) of both the sheet surface on which one resin layer (first resin layer) is provided and the sheet surface on which the other resin layer (second resin layer) is provided are each within the above range. The surface roughness (Ra) of the surface on the first resin layer side and the surface on the second resin layer side may be the same value, or may be different values within a range of 12.0 nm or less.
[0016] The surface roughness (Ra) of the sheet is a value measured by an optical interference type non-contact surface profiler in accordance with JIS B 0601:1994. For example, an optical interference type non-contact surface profiler such as the VertScan2.0 non-contact surface / layer cross-sectional profile measuring system R5500GML manufactured by Ryoka Systems Co., Ltd. can be used. The surface roughness is measured using a 10x objective lens in a measurement range of 470μm×350μm, and the arithmetic mean roughness (Ra) is calculated from the average value.
[0017] The sheet of the present invention has the above-mentioned configuration, and therefore has high transparency. It is known that the transparency of a sheet containing fine fibrous cellulose is higher than that of a sheet containing coarse cellulose fibers, but the sheet of the present invention has realized a high level of high transparency that could not be achieved by conventional fine fibrous cellulose-containing sheets. As such, the sheet of the present invention is an extremely transparent sheet, and is therefore useful, for example, as an optical member or a sheet for bonding optical members. In addition to the use of optical members, it is also suitable for uses requiring high transparency.
[0018] The transparency of the sheet can be evaluated by measuring the haze of the sheet. Here, the haze of the sheet is a value measured using a haze meter in accordance with JIS K 7136:2000. As the haze meter, for example, HM-150 manufactured by Murakami Color Research Laboratory Co., Ltd. can be used. In this specification, when the haze of the sheet is less than 0.5%, the transparency of the sheet can be evaluated as high.
[0019] The total light transmittance of the sheet is preferably 85% or more, more preferably 90% or more. Here, the total light transmittance of the sheet is a value measured using a haze meter in accordance with JIS K 7361-1:1997. As the haze meter, for example, HM-150 manufactured by Murakami Color Research Laboratory Co., Ltd. can be used.
[0020] The tensile modulus of the sheet at 23°C and 50% relative humidity is preferably 2.5 GPa or more, more preferably 5 GPa or more, even more preferably 7 GPa or more, even more preferably 9 GPa or more, and particularly preferably 10 GPa or more. The tensile modulus of the sheet at 23°C and 50% relative humidity is preferably 30 GPa or less. The tensile modulus of the sheet is a value measured in accordance with JIS P 8113:2006, and the tensile modulus is a value calculated from the maximum positive slope value in the SS curve (stress-strain curve).
[0021] The sheet of the present invention can exhibit excellent water resistance. Thus, the sheet of the present invention is a sheet that combines high transparency and water resistance. The water resistance of the sheet can be evaluated by the water contact angle of the surface of the sheet. Specifically, the water contact angle of both surfaces of the sheet is preferably 75° or more, more preferably 80° or more. That is, it is preferable that the water contact angles of both the sheet surface on which one resin layer (first resin layer) is provided and the sheet surface on which the other resin layer (second resin layer) is provided are each within the above range. Here, the water contact angle of the sheet surface is the water contact angle 30 seconds after 4 μL of distilled water is dropped on the surface of the sheet. A dynamic water contact angle tester is used for the measurement. For example, 1100DAT manufactured by Fibro can be used as the dynamic water contact angle tester.
[0022] In the sheet of the present invention, the fiber layer and the resin layer show excellent interlayer adhesion. Here, the interlayer adhesion can be evaluated by the number of peeled masses of the resin layer. Specifically, in accordance with JIS K 5400:1990, 2 Then, cellophane tape (manufactured by Nichiban Co., Ltd.) was applied on top of the 100 pieces of cross-cut, and 1.5 kg / cm 2 The cellophane tape is then peeled off in a 90° direction, and the adhesion between the fiber layer and the resin layer is evaluated based on the number of peeled squares. The number of peeled squares is preferably less than 10 points, more preferably less than 5 points, and particularly preferably 0 points.
[0023] The total thickness of the sheet of the present invention is not particularly limited, but is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more. The total thickness of the sheet is preferably 1000 μm or less, more preferably 800 μm or less, and even more preferably 600 μm or less. The thickness of the sheet is preferably adjusted appropriately depending on the application.
[0024] The overall basis weight of the sheet is 10 g / m 2 It is preferable that the thickness is 20 g / m or more.2 More preferably, it is 30 g / m or more. 2 The total basis weight of the sheet is not particularly limited, but is preferably 5000 g / m 2 It is preferable that the thickness is less than 2500 g / m 2 More preferably, it is 1000 g / m or less. 2 More preferably, it is 500 g / m or less. 2 It is particularly preferable that the following is satisfied: The basis weight of the sheet is measured in accordance with JIS P 8124:2011.
[0025] The overall density of the sheet is 1.00 g / cm 3 It is preferable that the content is 1.20 g / cm or more. 3 More preferably, it is 1.30 g / cm or more. 3 More preferably, it is 1.40 g / cm or more. 3 More preferably, the density of the sheet is calculated by dividing the basis weight of the sheet by the thickness. The thickness of the sheet can be measured with a stylus thickness gauge (Millitron 1202D, manufactured by Mahr).
[0026] The moisture content (moisture content) of the sheet is preferably 15% by mass or less, more preferably 12% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less. Here, the moisture content of the sheet can be evaluated as follows. Specifically, the sheet is cut into a test piece of 5 cm x 5 cm, and the test piece is conditioned at 23°C and a relative humidity of 50% for 24 hours, and then dried in a thermostat at 105°C until it becomes completely dry. The weight of the test piece after conditioning is W (g), the weight of the test piece after drying is D, and the value calculated by (WD) / W x 100 is the moisture content (mass%) of the sheet. By setting the moisture content of the sheet within the above range, tensile properties such as tensile modulus can be improved.
[0027] The refractive index of the resin layer constituting the sheet is preferably 1.30 or more, more preferably 1.40 or more, and even more preferably 1.50 or more. The refractive index of the resin layer is preferably 1.70 or less, more preferably 1.65 or less, even more preferably 1.60 or less, even more preferably 1.57 or less, and particularly preferably 1.55 or less. Here, the refractive index of the resin layer is a value measured using an Abbe refractometer in accordance with JIS K 7142:2008. As the Abbe refractometer, for example, NAR-3T manufactured by ATAGO Co., Ltd. can be used. When measuring the refractive index of the resin layer, 0.5 mL of the resin coating liquid is applied onto a glass substrate (2 cm x 2 cm) for Abbe measurement, and heated at 100 ° C for 1 hour to form a resin layer. The resin layer formed on the glass substrate is not peeled off from the glass substrate, and is used as it is for measuring the refractive index.
[0028] The refractive index of the fiber layer constituting the sheet is preferably 1.51 or more, more preferably 1.53 or more. The refractive index of the fiber layer is preferably 1.60 or less, more preferably 1.58 or less, even more preferably 1.56 or less, and particularly preferably 1.54 or less. Here, the refractive index of the fiber layer is a value measured using an Abbe refractometer in accordance with JIS K 7142:2008. For example, the Abbe refractometer NAR-3T manufactured by ATAGO Co., Ltd. can be used.
[0029] The refractive index of the fiber layer and the refractive index of the resin layer are preferably close to each other. In this case, the refractive index ratio of the fiber layer to the resin layer (refractive index of the fiber layer / refractive index of the resin layer) is preferably 0.50 or more, preferably 0.80 or more, more preferably 0.95 or more, even more preferably 0.97 or more, and particularly preferably 0.98 or more. In addition, the refractive index ratio of the fiber layer to the resin layer (refractive index of the fiber layer / refractive index of the resin layer) is preferably 1.50 or less, more preferably 1.20 or less, even more preferably 1.10 or less, and particularly preferably 1.02 or less.
[0030] In particular, by setting the refractive index ratio of the fiber layer to the resin layer (refractive index of the fiber layer / refractive index of the resin layer) to 0.98 or more and 1.02 or less, it is possible to suppress the occurrence of ripples (rainbow unevenness) due to optical interference when the sheet is used as an optical member. In particular, when the refractive index of the fiber layer is set to 1.51 to 1.54 and the refractive index ratio (refractive index of the fiber layer / refractive index of the resin layer) is set to 0.98 or more and 1.02 or less, the occurrence of ripples can be more effectively suppressed.
[0031] (Resin layer) The resin layer is a layer whose main component is a natural resin or a synthetic resin. Here, the main component refers to a component contained in an amount of 50% by mass or more relative to the total mass of the resin layer. The resin content is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more relative to the total mass of the resin layer. The resin content may be 100% by mass.
[0032] In the present invention, the thickness of each resin layer is preferably 10 μm or less, more preferably 8 μm or less, even more preferably 6 μm or less, even more preferably 5 μm or less, and particularly preferably 4 μm or less. The thickness of each resin layer is preferably 0.1 μm or more. It is preferable that the values of both the first resin layer and the second resin layer are within the above range. Here, the thickness of the resin layer constituting the sheet is a value measured by cutting out a cross section of the sheet using an ultramicrotome UC-7 (manufactured by JEOL) and observing the cross section with an electron microscope, a magnifying glass, or visually.
[0033] Examples of natural resins include rosin-based resins such as rosin, rosin ester, and hydrogenated rosin ester.
[0034] Examples of synthetic resins include polycarbonate resin, polyester resin, polyethylene naphthalate resin, polyethylene resin, polypropylene resin, polyimide resin, polystyrene resin, urethane resin, acrylic resin, and fluororesin. Among them, the synthetic resin is preferably an amorphous resin, more preferably at least one selected from the group consisting of polycarbonate resin, urethane resin, acrylic resin, and fluororesin, and particularly preferably a polycarbonate resin. The acrylic resin also includes urethane acrylic resin.
[0035] Examples of the polycarbonate resin constituting the resin layer include aromatic polycarbonate resins and aliphatic polycarbonate resins. Specific examples of these polycarbonate resins are known, and examples of such polycarbonate resins include the polycarbonate resins described in JP 2010-023275 A.
[0036] The resin layer preferably contains a hydrophobic resin. In this specification, the hydrophobic resin is defined as a resin having a contact angle with water of 60 degrees or more in a dry state. Here, "in a dry state" means excluding a state in which the hydrophobic resin has affinity with water, such as when the hydrophobic resin is in an emulsion state.
[0037] The resin layer may contain an adhesion aid. Examples of the adhesion aid include a compound containing at least one selected from the group consisting of an isocyanate group, a carbodiimide group, an epoxy group, an oxazoline group, an amino group, and a silanol group, and an organosilicon compound. Examples of the organosilicon compound include a silane coupling agent condensate and a silane coupling agent. Among them, the adhesion aid is preferably a compound containing an isocyanate group (isocyanate compound), and the resin layer is preferably one containing an isocyanate compound.
[0038] The isocyanate compound may be a polyisocyanate compound or a polyfunctional isocyanate.Specific examples of the polyisocyanate compound include aromatic polyisocyanates having 6 to 20 carbon atoms excluding the carbon in the NCO group, aliphatic polyisocyanates having 2 to 18 carbon atoms, alicyclic polyisocyanates having 6 to 15 carbon atoms, aralkyl polyisocyanates having 8 to 15 carbon atoms, modified products of these polyisocyanates, and mixtures of two or more of these.Among these, alicyclic polyisocyanates having 6 to 15 carbon atoms, i.e., isocyanurates, are preferably used.
[0039] Specific examples of alicyclic polyisocyanates include isophorone diisocyanate (IPDI), dicyclohexylmethane-4,4'-diisocyanate (hydrogenated MDI), cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexene-1,2-dicarboxylate, 2,5-norbornane diisocyanate, and 2,6-norbornane diisocyanate.
[0040] The organic silicon compound may be a compound having a siloxane structure or a compound that forms a siloxane structure by condensation. For example, a silane coupling agent or a condensate of a silane coupling agent may be mentioned. The silane coupling agent may have a functional group other than an alkoxysilyl group, or may not have any other functional group. The functional group other than an alkoxysilyl group may be a vinyl group, an epoxy group, a styryl group, a methacryloxy group, an acryloxy group, an amino group, a ureido group, a mercapto group, a sulfide group, an isocyanate group, etc. The silane coupling agent used in the present invention is preferably a silane coupling agent containing a methacryloxy group.
[0041] Specific examples of silane coupling agents having methacryloxy groups in the molecule include methacryloxypropylmethyldimethoxysilane, methacryloxypropyltrimethoxysilane, methacryloxypropylmethyldiethoxysilane, methacryloxypropyltriethoxysilane, 1,3-bis(3-methacryloxypropyl)tetramethyldisiloxane, etc. Among them, at least one selected from methacryloxypropyltrimethoxysilane, methacryloxypropyltriethoxysilane, and 1,3-bis(3-methacryloxypropyl)tetramethyldisiloxane is preferably used. The silane coupling agent preferably contains three or more alkoxysilyl groups.
[0042] In the silane coupling agent, silanol groups are generated after hydrolysis, and it is preferable that at least a part of the silanol groups remain even after laminating the fiber layer. Since the silanol groups are hydrophilic groups, the adhesion between the resin layer and the fiber layer can be improved by increasing the hydrophilicity of the surface of the resin layer facing the fiber layer.
[0043] The adhesion aid may be contained in a state of being uniformly dispersed in the resin layer. Here, the state where the adhesion aid is uniformly dispersed in the resin layer refers to a state where the concentration of any two regions is not more than two times higher than the concentration of the other two regions when the concentrations of the adhesion aid are measured in the following three regions ((a) to (c)): (a) The region from the surface of the resin layer facing the fiber layer to 10% of the total thickness of the resin layer (b) A region from the surface of the resin layer opposite the surface of the fiber layer to 10% of the total thickness of the resin layer. (c) An area within ±5% (total 10%) of the total thickness from the center plane of the resin layer in the thickness direction
[0044] The adhesion aid may be unevenly distributed in the region of the resin layer on the fiber layer side. For example, when an organosilicon compound is used as the adhesion aid, the organosilicon compound may be unevenly distributed in the region of the resin layer on the fiber layer side. Here, the state in which the resin layer is unevenly distributed in the region on the fiber layer side refers to a state in which, when the two concentrations in the following regions ((d) and (e)) are measured, the difference between these concentrations is two-fold or more. (d) A region from the surface of the resin layer facing the fiber layer to 10% of the total thickness of the resin layer (e) An area within ±5% (total 10%) of the total thickness from the center plane of the resin layer in the thickness direction Here, the concentration of the adhesion aid is a value measured by an X-ray electron spectrometer or an infrared spectrophotometer, and is a value obtained by cutting out a cross-section of a specified area of the sheet with an ultramicrotome UC-7 (manufactured by JEOL) and measuring the cross-section with the same device.
[0045] An organosilicon compound-containing layer may be provided on the surface of the resin layer facing the fiber layer, and such a state is also included in the state in which the organosilicon compound is unevenly distributed in the region of the resin layer facing the fiber layer. The organosilicon compound-containing layer may be a coating layer formed by applying an organosilicon compound-containing coating liquid. In addition, when an organosilicon compound-containing layer is provided on the surface of the resin layer facing the fiber layer, in the above region (d), "the surface of the resin layer facing the fiber layer" shall be read as "the exposed surface of the organosilicon compound-containing layer", and "the entire thickness of the resin layer" shall be read as "the combined thickness of the resin layer and the organosilicon compound-containing layer".
[0046] The content of the adhesion assistant is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, relative to 100 parts by mass of the resin contained in the resin layer, and is preferably 40 parts by mass or less, more preferably 35 parts by mass or less, relative to 100 parts by mass of the resin contained in the resin layer. When the adhesion aid is an isocyanate compound, the content of the isocyanate compound is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and even more preferably 18 parts by mass or more, relative to 100 parts by mass of the resin contained in the resin layer. The content of the isocyanate compound is preferably 40 parts by mass or less, more preferably 35 parts by mass or less, and even more preferably 30 parts by mass or less, relative to 100 parts by mass of the resin contained in the resin layer. When the adhesion assistant is an organosilicon compound, the content of the organosilicon compound is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, based on 100 parts by mass of the resin contained in the resin layer, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, based on 100 parts by mass of the resin contained in the resin layer. By setting the content of the adhesion assistant within the above range, the adhesion between the fiber layer and the resin layer can be more effectively improved.
[0047] When the adhesion aid is an isocyanate compound, the content of the isocyanate group contained in the resin layer is preferably 0.5 mmol / g or more, more preferably 0.6 mmol / g or more, even more preferably 0.8 mmol / g or more, and particularly preferably 0.9 mmol / g or more. The content of the isocyanate group contained in the resin layer is preferably 3.0 mmol / g or less, more preferably 2.5 mmol / g or less, even more preferably 2.0 mmol / g or less, and particularly preferably 1.5 mmol / g or less.
[0048] The surface of the resin layer facing the fiber layer may be subjected to a surface treatment. Examples of the surface treatment method include corona treatment, plasma discharge treatment, UV irradiation treatment, electron beam irradiation treatment, and flame treatment. Among them, the surface treatment is preferably at least one selected from corona treatment and plasma discharge treatment. The plasma discharge treatment is preferably vacuum plasma discharge treatment.
[0049] The resin layer may contain optional components other than the synthetic resin, as long as the effects of the present invention are not impaired. Examples of optional components include known components used in the field of resin films, such as fillers, pigments, dyes, and ultraviolet absorbers.
[0050] In the present invention, the resin layer may be an ultraviolet-curable resin layer or a solvent-coated layer. In particular, the resin layer is preferably a solvent-coated layer. That is, the resin layer is preferably a layer formed by applying a resin coating liquid containing a solvent onto a fiber layer and curing the applied resin coating liquid. By forming the resin layer as a solvent-coated layer in this way, a sheet exhibiting high transparency can be efficiently manufactured.
[0051] When the resin layer is an ultraviolet curing type resin layer, the resin coating liquid preferably contains a photopolymerization initiator. For example, the resin layer can be formed by applying a resin coating liquid containing a solvent and a photopolymerization initiator onto a fiber layer, volatilizing the solvent by heating and drying, and then irradiating with ultraviolet light. The amount of irradiation with ultraviolet light is arbitrary as long as the photopolymerization initiator generates radicals.
[0052] (fiber layer) The fiber layer contains fibrous cellulose (fine fibrous cellulose) having a fiber width of 1000 nm or less. The content of the fine fibrous cellulose is preferably 10% by mass or more, more preferably 50% by mass or more, even more preferably 60% by mass or more, and even more preferably 70% by mass or more, based on the total mass of the fiber layer.
[0053] The thickness of the fiber layer is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more. The thickness of the fiber layer is preferably 1000 μm or less, more preferably 800 μm or less, and even more preferably 600 μm or less. Here, the thickness of the fiber layer constituting the sheet is a value measured by cutting out a cross section of the sheet with an ultramicrotome UC-7 (manufactured by JEOL) and observing the cross section with an electron microscope, a magnifying glass, or visually.
[0054] The density of the fiber layer is 1.0 g / cm 3 It is preferable that the content is 1.1 g / cm or more. 3 More preferably, it is 1.2 g / cm or more. 3 It is more preferable that the density of the fiber layer is 1.8 g / cm or more. 3 It is preferable that the density is 1.7 g / cm or less. 3 More preferably, it is 1.6 g / cm or less. 3 It is even more preferable that:
[0055] The density of the fiber layer is calculated from the basis weight and thickness of the fiber layer in accordance with JIS P 8118: 2014. The basis weight of the fiber layer can be calculated in accordance with JIS P 8124: 2011 by cutting the sheet using an ultramicrotome UC-7 (manufactured by JEOL) so that only the fiber layer remains. When the fiber layer contains any component other than fine fibrous cellulose, the density of the fiber layer is the density including any component other than fine fibrous cellulose.
[0056] The present invention is characterized in that the fiber layer is a non-porous layer. Here, the fiber layer being non-porous means that the density of the entire fiber layer is 1.0 g / cm 3 The density of the entire fiber layer is 1.0 g / cm or more. 3 If it is equal to or higher than this, it means that the void ratio contained in the fiber layer is suppressed to a predetermined value or less, and it is distinguished from a porous sheet or layer. The non-porous nature of the fibrous layer is also characterized by a porosity of 15 volume % or less. The porosity of the fibrous layer referred to here is calculated simply by the following formula (a). Formula (a): Porosity (volume%) = {1-B / (M×A×t)}×100 where A is the area of the fiber layer (cm 2 ), t is the thickness of the fiber layer (cm), B is the mass of the fiber layer (g), and M is the density of the solid content constituting the fiber layer.
[0057] <Fine fibrous cellulose> The fiber layer contains fibrous cellulose having a fiber width of 1000 nm or less. The fiber width of the fibrous cellulose is preferably 100 nm or less, more preferably 8 nm or less. This makes it possible to more effectively increase dispersibility in a solvent, and makes it easier to obtain a fiber layer with high strength and high transparency.
[0058] The fiber width of fibrous cellulose can be measured, for example, by observation under an electron microscope. The average fiber width of fibrous cellulose is, for example, 1000 nm or less. The average fiber width of fibrous cellulose is, for example, preferably 2 nm or more and 1000 nm or less, more preferably 2 nm or more and 100 nm or less, even more preferably 2 nm or more and 50 nm or less, and particularly preferably 2 nm or more and 10 nm or less. By making the average fiber width of fibrous cellulose 2 nm or more, it becomes easier to suppress dissolution of cellulose molecules in water. The fibrous cellulose is, for example, monofilamentous cellulose.
[0059] The average fiber width of fibrous cellulose is measured, for example, using an electron microscope as follows. First, an aqueous suspension of fibrous cellulose with a concentration of 0.05% by mass or more and 0.1% by mass or less is prepared, and this suspension is cast on a hydrophilically treated carbon film-coated grid to prepare a sample for TEM observation. When wide fibers are included, an SEM image of the surface cast on glass may be observed. Next, observation is performed using an electron microscope image at a magnification of 1000x, 5000x, 10000x, or 50000x depending on the width of the fiber to be observed. However, the sample, observation conditions, and magnification are adjusted to satisfy the following conditions. (1) A straight line X is drawn at any point within the observed image, and 20 or more fibers intersect with the straight line X. (2) Within the same image, draw a line Y that intersects the line perpendicularly, and have 20 or more fibers intersect with the line Y. For observation images that satisfy the above conditions, the width of the fibers that intersect with lines X and Y is visually read. In this manner, three or more sets of observation images of at least the surface portions that do not overlap each other are obtained. Next, for each image, the width of the fibers that intersect with lines X and Y is read. In this manner, the width of at least 20 fibers x 2 x 3 = 120 fibers is read. The average value of the read fiber widths is then determined as the average fiber width of the fibrous cellulose.
[0060] The fiber length of the fibrous cellulose is not particularly limited, but is preferably 0.1 μm or more and 1000 μm or less, more preferably 0.1 μm or more and 800 μm or less, and even more preferably 0.1 μm or more and 600 μm or less. By setting the fiber length within the above range, destruction of the crystalline region of the fibrous cellulose can be suppressed. In addition, it is also possible to set the slurry viscosity of the fibrous cellulose to an appropriate range. The fiber length of the fibrous cellulose can be determined, for example, by image analysis using TEM, SEM, or AFM.
[0061] The fibrous cellulose preferably has an I-type crystal structure. Here, the fact that the fibrous cellulose has an I-type crystal structure can be identified from a diffraction profile obtained from a wide-angle X-ray diffraction photograph using CuKα (λ=1.5418 Å) monochromatized with graphite. Specifically, it can be identified from the presence of typical peaks at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°. The proportion of I-type crystal structure in the fine fibrous cellulose is, for example, preferably 30% or more, more preferably 40% or more, and even more preferably 50% or more. This can be expected to provide even more excellent performance in terms of heat resistance and low linear thermal expansion coefficient. The degree of crystallinity can be determined by measuring the X-ray diffraction profile and using the pattern in a conventional manner (Seagal et al., Textile Research Journal, Vol. 29, p. 786, 1959).
[0062] The axial ratio (fiber length / fiber width) of the fibrous cellulose is not particularly limited, but is preferably, for example, 20 to 10,000, and more preferably 50 to 1,000. By setting the axial ratio to the above lower limit or more, a sheet containing fine fibrous cellulose can be easily formed. By setting the axial ratio to the above upper limit or less, it is preferable in that, for example, when the fibrous cellulose is treated as a dispersion liquid, handling such as dilution is facilitated.
[0063] The fibrous cellulose in this embodiment has, for example, both crystalline and non-crystalline regions. In particular, fine fibrous cellulose having both crystalline and non-crystalline regions and a high axial ratio is realized by a method for producing fine fibrous cellulose, which will be described later.
[0064] The fibrous cellulose preferably has an ionic substituent. When the fibrous cellulose has an ionic substituent, the dispersibility of the fibrous cellulose in a dispersion medium can be improved, and the defibration efficiency in the defibration treatment can be increased. The ionic substituent can include, for example, either one or both of an anionic group and a cationic group. In this embodiment, it is particularly preferable that the ionic substituent has an anionic group.
[0065] Examples of anionic groups as ionic substituents include phosphorus oxoacid groups or substituents derived from phosphorus oxoacid groups (sometimes simply referred to as phosphorus oxoacid groups), carboxy groups or substituents derived from carboxy groups (sometimes simply referred to as carboxy groups), sulfone groups or substituents derived from sulfone groups (sometimes simply referred to as sulfone groups), xanthate groups, phosphonic groups, phosphine groups, carboxyalkyl groups (including carboxymethyl groups), etc. When a sulfone group or a substituent derived from a sulfone group is introduced via an ester bond, the substituent may be referred to as a sulfur oxoacid group or a substituent derived from a sulfur oxoacid group (sometimes simply referred to as a sulfur oxoacid group). Among them, the anionic group is preferably at least one selected from the group consisting of a phosphorus oxoacid group, a substituent derived from a phosphorus oxoacid group, a carboxy group, a substituent derived from a carboxy group, a carboxymethyl group, a sulfur oxoacid group, and a substituent derived from a sulfur oxoacid group, more preferably at least one selected from the group consisting of a phosphorus oxoacid group, a substituent derived from a phosphorus oxoacid group, a carboxy group, a substituent derived from a carboxy group, a sulfur oxoacid group, and a substituent derived from a sulfur oxoacid group, and is particularly preferably a phosphorus oxoacid group. By introducing a phosphorus oxoacid group as the anionic group, the dispersibility of the fibrous cellulose can be further increased even under alkaline or acidic conditions, for example, and as a result, a fiber layer with high strength and high transparency can be easily obtained.
[0066] The phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group is, for example, a substituent represented by the following formula (1). A plurality of types of the substituent represented by the following formula (1) may be introduced into each fibrous cellulose. In this case, the plurality of introduced substituents represented by the following formula (1) may be the same or different.
[0067] [ka]
[0068] In formula (1), a, b, and n are natural numbers, and m is an arbitrary number (where a=b×m). At least one of the n α and α' is O. - and the rest are R or OR. Note that all of α and α' are O - The n α's may all be the same or may be different. b+ is a cation of one or more valences consisting of organic or inorganic substances.
[0069] Each R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an unsaturated cyclic hydrocarbon group, an aromatic group, or a group derived therefrom. In formula (1), n is preferably 1.
[0070] Examples of saturated linear hydrocarbon groups include, but are not limited to, methyl, ethyl, n-propyl, or n-butyl groups. Examples of saturated branched hydrocarbon groups include, but are not limited to, i-propyl or t-butyl groups. Examples of saturated cyclic hydrocarbon groups include, but are not limited to, cyclopentyl or cyclohexyl groups. Examples of unsaturated linear hydrocarbon groups include, but are not limited to, vinyl or allyl groups. Examples of unsaturated branched hydrocarbon groups include, but are not limited to, i-propenyl or 3-butenyl groups. Examples of unsaturated cyclic hydrocarbon groups include, but are not limited to, cyclopentenyl or cyclohexenyl groups. Examples of aromatic groups include, but are not limited to, phenyl or naphthyl groups.
[0071] In addition, the derivative group in R is a carboxy group, a carboxylate group (-COO -), a functional group in which at least one functional group selected from functional groups such as a hydroxy group, an amino group, and an ammonium group is added or substituted, but is not particularly limited. The number of carbon atoms constituting the main chain of R is not particularly limited, but is preferably 20 or less, more preferably 10 or less. By setting the number of carbon atoms constituting the main chain of R within the above range, the molecular weight of the phosphorus oxoacid group can be set to an appropriate range, which facilitates penetration into the fiber raw material and increases the yield of fibrous cellulose. Note that when there are multiple R in formula (1) or when multiple types of substituents represented by the above formula (1) are introduced into the fibrous cellulose, the multiple Rs present may be the same or different.
[0072] β b+ is a monovalent or higher cation made of an organic or inorganic substance. An example of the monovalent or higher cation made of an organic substance is an organic onium ion. An example of the organic onium ion is an organic ammonium ion or an organic phosphonium ion. An example of the organic ammonium ion is an aliphatic ammonium ion or an aromatic ammonium ion, and an example of the organic phosphonium ion is an aliphatic phosphonium ion or an aromatic phosphonium ion. An example of the monovalent or higher cation made of an inorganic substance is an ion of an alkali metal such as sodium, potassium, or lithium, an ion of a divalent metal such as calcium or magnesium, a hydrogen ion, an ammonium ion, or the like. In addition, in formula (1), β b+ When a plurality of substituents represented by the above formula (1) are present or when a plurality of substituents represented by the above formula (1) are introduced into the fibrous cellulose, the plurality of β b+ may be the same or different. The organic or inorganic cations of monovalent or higher are β b+ Sodium or potassium ions are preferred because they are less likely to yellow when the fiber raw material containing the cation is heated and are easy to use industrially, but there is no particular limitation.
[0073] More specifically, the phosphorus oxo acid group or a substituent derived from the phosphorus oxo acid group is a phosphoric acid group (-PO 3 H 2 ), salts of phosphoric acid groups, phosphorous acid groups (phosphonic acid groups) (-PO 2 H 2 ), and salts of phosphorous acid group (phosphonic acid group). The phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group may be a group in which a phosphoric acid group is condensed (e.g., a pyrophosphate group), a group in which a phosphonic acid is condensed (e.g., a polyphosphonic acid group), a phosphoric ester group (e.g., a monomethyl phosphate group, a polyoxyethylene alkyl phosphate group), an alkyl phosphonic acid group (e.g., a methyl phosphonic acid group), and the like.
[0074] The sulfur oxoacid group (sulfur oxoacid group or a substituent derived from a sulfur oxoacid group) is, for example, a substituent represented by the following formula (2). A plurality of substituents represented by the following formula (2) may be introduced into each fibrous cellulose. In this case, the plurality of introduced substituents represented by the following formula (2) may be the same or different.
[0075] [ka]
[0076] In the above structural formula, b and n are natural numbers, p is 0 or 1, and m is an arbitrary number (where 1=b×m). When n is 2 or more, the multiple p's may be the same or different. In the above structural formula, β b+is a monovalent or higher cation made of an organic or inorganic substance. Examples of the monovalent or higher cation made of an organic substance include organic onium ions. Examples of the organic onium ions include organic ammonium ions and organic phosphonium ions. Examples of the organic ammonium ions include aliphatic ammonium ions and aromatic ammonium ions, and examples of the organic phosphonium ions include aliphatic phosphonium ions and aromatic phosphonium ions. Examples of the monovalent or higher cation made of an inorganic substance include ions of alkali metals such as sodium, potassium, and lithium, ions of divalent metals such as calcium and magnesium, hydrogen ions, and ammonium ions. When multiple types of substituents represented by the above formula (2) are introduced into the fibrous cellulose, the multiple β b+ may be the same or different. The organic or inorganic cations of monovalent or higher are β b+ Sodium or potassium ions are preferred because they are less likely to yellow when the fiber raw material containing the cation is heated and are easy to use industrially, but there is no particular limitation.
[0077] The amount of ionic substituent introduced into fibrous cellulose is, for example, preferably 0.10 mmol / g or more per 1 g (mass) of fibrous cellulose, more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 1.00 mmol / g or more. The amount of ionic substituent introduced into fibrous cellulose is, for example, preferably 5.20 mmol / g or less per 1 g (mass) of fibrous cellulose, more preferably 3.65 mmol / g or less, even more preferably 3.50 mmol / g or less, and even more preferably 3.00 mmol / g or less. By setting the amount of ionic substituent introduced within the above range, it is possible to easily refine the fiber raw material and to increase the stability of the fibrous cellulose. Here, the denominator in the unit mmol / g is calculated based on the fact that the counter ion of the ionic substituent is a hydrogen ion (H + ) indicates the mass of fibrous cellulose.
[0078] The amount of ionic substituents introduced into the fibrous cellulose can be measured, for example, by neutralization titration, in which an alkali such as an aqueous sodium hydroxide solution is added to a slurry containing the obtained fibrous cellulose to determine the change in pH, thereby measuring the amount introduced.
[0079] 2 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having phosphorus oxo acid groups as ionic substituents and pH. The amount of phosphorus oxo acid groups introduced into the fibrous cellulose is measured, for example, as follows. First, a slurry containing fibrous cellulose is treated with a strongly acidic ion exchange resin. If necessary, the measurement target may be subjected to a defibration treatment similar to the defibration treatment step described below prior to the treatment with the strongly acidic ion exchange resin. Next, the change in pH is observed while adding the aqueous sodium hydroxide solution, and a titration curve such as that shown in the upper part of Figure 2 is obtained. In the titration curve shown in the upper part of Figure 2, the measured pH is plotted against the amount of alkali added, and in the titration curve shown in the lower part of Figure 2, the increment (derivative value) of pH (1 / mmol) against the amount of alkali added is plotted. In this neutralization titration, two points are confirmed in the curve plotting the measured pH against the amount of alkali added, where the increment (derivative value of pH with respect to the amount of alkali added) is maximum. Of these, the first maximum point of the increment obtained after starting to add the alkali is called the first endpoint, and the next maximum point of the increment is called the second endpoint. The amount of alkali required from the start of titration to the first end point is equal to the amount of the first dissociated acid of the fibrous cellulose contained in the slurry used for titration, the amount of alkali required from the first end point to the second end point is equal to the amount of the second dissociated acid of the fibrous cellulose contained in the slurry used for titration, and the amount of alkali required from the start of titration to the second end point is equal to the total amount of dissociated acid of the fibrous cellulose contained in the slurry used for titration. The value obtained by dividing the amount of alkali required from the start of titration to the first end point by the solid content (g) in the slurry to be titrated is the amount of phosphorus oxoacid group introduced (mmol / g). Note that when simply referring to the amount of phosphorus oxoacid group introduced (or the amount of phosphorus oxoacid group), it refers to the amount of the first dissociated acid. In FIG. 2, the region from the start of titration to the first end point is called the first region, and the region from the first end point to the second end point is called the second region. For example, when the phosphorus oxoacid group is a phosphate group and this phosphate group undergoes condensation, the amount of weak acid groups (amount of second dissociated acid) in the phosphorus oxoacid group appears to decrease, and the amount of alkali required in the second region becomes smaller than the amount of alkali required in the first region. On the other hand, the amount of strong acid groups (amount of first dissociated acid) in the phosphorus oxoacid group coincides with the amount of phosphorus atoms regardless of the presence or absence of condensation. In addition, when the phosphorus oxoacid group is a phosphite group, the weak acid groups no longer exist in the phosphorus oxoacid group, so the amount of alkali required in the second region becomes smaller or may become zero. In this case, there is only one point on the titration curve where the pH increment is maximum.
[0080] The above-mentioned amount of phosphorus oxoacid groups introduced (mmol / g) indicates the amount of phosphorus oxoacid groups possessed by the acid-type fibrous cellulose (hereinafter referred to as the amount of phosphorus oxoacid groups (acid type)), since the denominator indicates the mass of the acid-type fibrous cellulose. On the other hand, when the counter ion of the phosphorus oxoacid group is replaced with an arbitrary cation C so as to be the charge equivalent, the amount of phosphorus oxoacid groups possessed by the fibrous cellulose in which the cation C is the counter ion (hereinafter referred to as the amount of phosphorus oxoacid groups (C type)) can be obtained by converting the denominator to the mass of the fibrous cellulose when the cation C is the counter ion. That is, it is calculated according to the following formula. Amount of phosphorus oxoacid group (C type) = Amount of phosphorus oxoacid group (acid type) / {1+(W-1)×A / 1000} A [mmol / g]: total amount of anions derived from phosphorus oxoacid groups in fibrous cellulose (total amount of dissociated acid from phosphorus oxoacid groups) W: Formula weight per valence of cation C (for example, Na is 23, Al is 9)
[0081] 3 is a graph showing the relationship between the amount of NaOH dropped onto a dispersion containing fibrous cellulose having a carboxy group as an ionic substituent and the pH. The amount of carboxy group introduced into the fibrous cellulose is measured, for example, as follows. First, a dispersion liquid containing fibrous cellulose is treated with a strongly acidic ion exchange resin. If necessary, a defibration treatment similar to the defibration treatment step described below may be performed on the measurement target prior to the treatment with the strongly acidic ion exchange resin. Next, the change in pH is observed while adding the aqueous sodium hydroxide solution, and a titration curve as shown in the upper part of FIG. 3 is obtained. In the titration curve shown in the upper part of FIG. 3, the measured pH is plotted against the amount of added alkali, and in the titration curve shown in the lower part of FIG. 3, the increment (differential value) (1 / mmol) of pH against the amount of added alkali is plotted. In this neutralization titration, one point where the increment (differential value of pH against the amount of added alkali) is maximum is confirmed in the curve plotting the measured pH against the amount of added alkali, and this maximum point is called the first end point. Here, the region from the start of titration to the first end point in FIG. 3 is called the first region. The amount of alkali required in the first region is equal to the amount of carboxyl groups in the dispersion used for titration. The amount of alkali required in the first region of the titration curve (mmol) is divided by the solid content (g) in the dispersion containing the fibrous cellulose to be titrated to calculate the amount of carboxyl groups introduced (mmol / g).
[0082] The above-mentioned amount of carboxyl groups introduced (mmol / g) indicates the amount of carboxyl groups in the acid-type fibrous cellulose (hereinafter referred to as the amount of carboxyl groups (acid type)) since the denominator is the mass of the acid-type fibrous cellulose. On the other hand, when the counter ion of the carboxyl group is replaced with any cation C so as to be the charge equivalent, the amount of carboxyl groups in the fibrous cellulose in which the cation C is the counter ion (hereinafter referred to as the amount of carboxyl groups (C type)) can be obtained by converting the denominator to the mass of the fibrous cellulose when the cation C is the counter ion. That is, it is calculated by the following formula. Carboxylic acid amount (C type) = Carboxylic acid amount (acid type) / {1 + (W-1) x (Carboxylic acid amount (acid type)) / 1000} W: Formula weight per valence of cation C (for example, Na is 23, Al is 9)
[0083] In measuring the amount of ionic substituents by titration, if the amount of sodium hydroxide solution dropped is too large or the titration interval is too short, the amount of ionic substituents may be lower than the actual amount, and an accurate value may not be obtained. As an appropriate amount of drop and titration interval, for example, it is preferable to titrate 10 to 50 μL of 0.1N sodium hydroxide solution every 5 to 30 seconds. In addition, in order to eliminate the influence of carbon dioxide dissolved in the fibrous cellulose-containing slurry, it is preferable to measure while blowing an inert gas such as nitrogen gas into the slurry from 15 minutes before the start of titration until the end of titration.
[0084] The amount of sulfonic groups introduced into fibrous cellulose can be calculated by wet ashing the fibrous cellulose using perchloric acid and concentrated nitric acid, diluting it at an appropriate ratio, and measuring the amount of sulfur by ICP atomic emission spectrometry. The amount of sulfur divided by the bone dry mass of the fibrous cellulose sample is the amount of sulfonic groups (unit: mmol / g).
[0085] <Production process of fine fibrous cellulose> <Textile raw materials> Fine fibrous cellulose is produced from a fiber raw material containing cellulose. The fiber raw material containing cellulose is not particularly limited, but it is preferable to use pulp because it is easily available and inexpensive. Examples of pulp include wood pulp, non-wood pulp, and deinked pulp. Examples of wood pulp include, but are not particularly limited to, chemical pulp such as hardwood kraft pulp (LBKP), softwood kraft pulp (NBKP), sulfite pulp (SP), dissolving pulp (DP), soda pulp (AP), unbleached kraft pulp (UKP) and oxygen bleached kraft pulp (OKP), semi-chemical pulp such as semi-chemical pulp (SCP) and chemi-ground wood pulp (CGP), mechanical pulp such as groundwood pulp (GP) and thermomechanical pulp (TMP, BCTMP), etc. Examples of non-wood pulp include, but are not particularly limited to, cotton-based pulp such as cotton linters and cotton lint, and non-wood-based pulp such as hemp, wheat straw, and bagasse. The deinked pulp is not particularly limited, but may be deinked pulp made from waste paper. The pulp of this embodiment may be one of the above, or may be a mixture of two or more. Among the above pulps, wood pulp and deinked pulp are preferable from the viewpoint of availability. Among wood pulps, chemical pulp is more preferable, and kraft pulp and sulfite pulp are even more preferable, from the viewpoint of a high cellulose ratio and a high yield of fine fibrous cellulose during defibration treatment, and of small decomposition of cellulose in the pulp and of obtaining long-fiber fine fibrous cellulose with a large axial ratio. The viscosity tends to be high when long-fiber fine fibrous cellulose with a large axial ratio is used.
[0086] As a fiber raw material containing cellulose, for example, cellulose contained in sea squirts and bacterial cellulose produced by acetic acid bacteria can be used. Also, instead of a fiber raw material containing cellulose, a fiber formed by a linear nitrogen-containing polysaccharide polymer such as chitin or chitosan can be used.
[0087] <Phosphorus oxo acid group introduction step> The manufacturing process of fine fibrous cellulose preferably includes a step of introducing an ionic substituent, and an example of the step of introducing an ionic substituent is a step of introducing a phosphorus oxo acid group. The step of introducing a phosphorus oxo acid group is a step of reacting a hydroxyl group possessed by a fiber raw material containing cellulose with at least one compound (hereinafter also referred to as "compound A") selected from compounds capable of introducing a phosphorus oxo acid group, on the fiber raw material containing cellulose. This step results in a fiber into which a phosphorus oxo acid group has been introduced.
[0088] In the phosphorus oxoacid group introduction step according to this embodiment, the reaction of the cellulose-containing fiber raw material with compound A may be carried out in the presence of at least one selected from urea and its derivatives (hereinafter also referred to as "compound B"). Alternatively, the reaction of the cellulose-containing fiber raw material with compound A may be carried out in the absence of compound B.
[0089] An example of a method for acting compound A on a fiber raw material in the presence of compound B includes a method of mixing compound A and compound B with a fiber raw material in a dry state, a wet state, or a slurry state. Of these, it is preferable to use a fiber raw material in a dry state or a wet state, and it is particularly preferable to use a fiber raw material in a dry state, because the reaction is highly uniform. The form of the fiber raw material is not particularly limited, but it is preferable to use a cotton-like or thin sheet-like form. Compound A and compound B can be added to the fiber raw material in a powder form, a solution form dissolved in a solvent, or a melted state by heating to a melting point or higher. Of these, it is preferable to add them in a solution form dissolved in a solvent, especially in an aqueous solution form, because the reaction is highly uniform. Compound A and compound B may be added to the fiber raw material simultaneously, separately, or as a mixture. The method of adding compound A and compound B is not particularly limited, but when compound A and compound B are in a solution form, the fiber raw material may be immersed in the solution to absorb the liquid and then removed, or the solution may be dropped onto the fiber raw material. In addition, the required amounts of compound A and compound B may be added to the fiber raw material, or excess amounts of compound A and compound B may be added to the fiber raw material, respectively, and then the excess compound A and compound B may be removed by squeezing or filtration.
[0090] The compound A used in this embodiment may be any compound that has a phosphorus atom and can form an ester bond with cellulose, and may include, but is not limited to, phosphoric acid or a salt thereof, phosphorous acid or a salt thereof, dehydrated condensed phosphoric acid or a salt thereof, and anhydrous phosphoric acid (diphosphorus pentoxide). Phosphoric acid may be used with various purities, for example, 100% phosphoric acid (orthophosphoric acid) or 85% phosphoric acid. Phosphorous acid may be 99% phosphorous acid (phosphonic acid). Dehydrated condensed phosphoric acid is a phosphoric acid in which two or more molecules are condensed by a dehydration reaction, and examples of the phosphoric acid include pyrophosphoric acid and polyphosphoric acid. Phosphates, phosphites, and dehydrated condensed phosphates include lithium salts, sodium salts, potassium salts, and ammonium salts of phosphoric acid, phosphorous acid, or dehydrated condensed phosphoric acid, and these may be neutralized to various degrees. Among these, from the viewpoints of high introduction efficiency of phosphate groups, easier improvement of defibration efficiency in the defibration step described below, low cost, and ease of industrial application, phosphoric acid, sodium salt of phosphoric acid, potassium salt of phosphoric acid, ammonium salt of phosphoric acid, or phosphorous acid, sodium salt of phosphorous acid, potassium salt of phosphorous acid, or ammonium salt of phosphorous acid are preferred, and phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, or phosphorous acid, sodium phosphite, and sodium hydrogen phosphite are more preferred.
[0091] The amount of compound A added to the fiber raw material is not particularly limited, but for example, when the amount of compound A added is converted into the amount of phosphorus atoms, the amount of phosphorus atoms added to the fiber raw material (bone dry mass) is preferably 0.5% by mass or more and 100% by mass or less, more preferably 1% by mass or more and 50% by mass or less, and even more preferably 2% by mass or more and 30% by mass or less. By setting the amount of phosphorus atoms added to the fiber raw material within the above range, the yield of fine fibrous cellulose can be further improved. On the other hand, by setting the amount of phosphorus atoms added to the fiber raw material to the above upper limit or less, a balance between the effect of improving the yield and the cost can be achieved.
[0092] The compound B used in this embodiment is at least one selected from urea and its derivatives as described above. Examples of compound B include urea, biuret, 1-phenylurea, 1-benzylurea, 1-methylurea, and 1-ethylurea. From the viewpoint of improving the uniformity of the reaction, it is preferable to use compound B as an aqueous solution. In addition, from the viewpoint of further improving the uniformity of the reaction, it is preferable to use an aqueous solution in which both compound A and compound B are dissolved.
[0093] The amount of compound B added relative to the fiber raw material (bone dry mass) is not particularly limited, but is preferably, for example, 1 mass% or more and 500 mass% or less, more preferably 10 mass% or more and 400 mass% or less, and even more preferably 100 mass% or more and 350 mass% or less.
[0094] In the reaction of a fiber raw material containing cellulose with compound A, in addition to compound B, for example, amides or amines may be included in the reaction system. Examples of amides include formamide, dimethylformamide, acetamide, and dimethylacetamide. Examples of amines include methylamine, ethylamine, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, pyridine, ethylenediamine, and hexamethylenediamine. Among these, triethylamine in particular is known to act as a good reaction catalyst.
[0095] In the phosphorus oxo acid group introduction step, it is preferable to add or mix the compound A or the like to the fiber raw material, and then heat-treat the fiber raw material. It is preferable to select a temperature for the heat treatment that allows efficient introduction of the phosphorus oxo acid group while suppressing thermal decomposition and hydrolysis of the fiber. The heat treatment temperature is, for example, preferably 50°C to 300°C, more preferably 100°C to 250°C, and even more preferably 130°C to 200°C. In addition, for the heat treatment, equipment having various heat media can be used, such as a stirring dryer, a rotary dryer, a disk dryer, a roll-type heater, a plate-type heater, a fluidized bed dryer, a band-type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far-infrared heater, a microwave heater, or a high-frequency dryer.
[0096] In the heat treatment according to the present embodiment, for example, a method of adding compound A to a thin sheet-like fiber raw material by a method such as impregnation, followed by heating, or a method of heating while kneading or stirring the fiber raw material and compound A in a kneader or the like, can be adopted. This makes it possible to suppress unevenness in the concentration of compound A in the fiber raw material and introduce phosphorus oxoacid groups more uniformly onto the surface of the cellulose fibers contained in the fiber raw material. This is believed to be due to the fact that when water molecules move to the surface of the fiber raw material as it dries, the dissolved compound A can be prevented from being attracted to the water molecules by surface tension and moving to the surface of the fiber raw material in the same manner (i.e., causing unevenness in the concentration of compound A).
[0097] In addition, the heating device used in the heat treatment is preferably a device that can constantly discharge, for example, the moisture held by the slurry and the moisture generated in the dehydration condensation (phosphorylation) reaction between compound A and hydroxyl groups contained in cellulose or the like in the fiber raw material, outside the device system. Examples of such heating devices include ovens that use a blowing system. By constantly discharging the moisture within the device system, it is possible to suppress the hydrolysis reaction of phosphate ester bonds, which is the reverse reaction of phosphate esterification, and also to suppress acid hydrolysis of the sugar chains in the fibers. This makes it possible to obtain fine fibrous cellulose with a high axial ratio.
[0098] The time for the heat treatment is, for example, preferably from 1 second to 300 minutes after the moisture is substantially removed from the fiber raw material, more preferably from 1 second to 1000 seconds, and even more preferably from 10 seconds to 800 seconds. In this embodiment, the introduction amount of phosphorus oxo acid groups can be kept within a preferred range by setting the heating temperature and heating time within appropriate ranges.
[0099] The phosphorus oxo acid group introduction step may be carried out at least once, but may also be carried out twice or more. By carrying out the phosphorus oxo acid group introduction step twice or more, a large number of phosphorus oxo acid groups can be introduced into the fiber raw material.
[0100] The amount of phosphorus oxoacid groups introduced into the fiber raw material is, for example, preferably 0.10 mmol / g or more per gram (mass) of fine fibrous cellulose, more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 1.00 mmol / g or more. The amount of phosphorus oxoacid groups introduced into the fiber raw material is, for example, preferably 5.20 mmol / g or less per gram (mass) of fine fibrous cellulose, more preferably 3.65 mmol / g or less, and even more preferably 3.00 mmol / g or less. By setting the amount of phosphorus oxoacid groups introduced within the above range, it is possible to easily fine the fiber raw material and to increase the stability of the fine fibrous cellulose.
[0101] <Carboxy group introduction step> The process for producing fine fibrous cellulose may include, for example, a carboxyl group introduction step as an ionic substituent introduction step. The carboxyl group introduction step is carried out by subjecting a fiber raw material containing cellulose to an oxidation treatment such as ozone oxidation, oxidation by the Fenton method, or TEMPO oxidation treatment, or treating the raw material with a compound having a carboxylic acid-derived group or a derivative thereof, or an acid anhydride of a compound having a carboxylic acid-derived group or a derivative thereof.
[0102] Examples of compounds having a group derived from a carboxylic acid include, but are not limited to, dicarboxylic acid compounds such as maleic acid, succinic acid, phthalic acid, fumaric acid, glutaric acid, adipic acid, and itaconic acid, and tricarboxylic acid compounds such as citric acid and aconitic acid. Examples of derivatives of compounds having a group derived from a carboxylic acid include, but are not limited to, imidized products of acid anhydrides of compounds having a carboxy group, and derivatives of acid anhydrides of compounds having a carboxy group. Examples of imidized products of acid anhydrides of compounds having a carboxy group include, but are not limited to, imidized products of dicarboxylic acid compounds such as maleimide, succinimide, and phthalimide.
[0103] The acid anhydride of a compound having a group derived from a carboxylic acid is not particularly limited, but examples thereof include acid anhydrides of dicarboxylic acid compounds such as maleic anhydride, succinic anhydride, phthalic anhydride, glutaric anhydride, adipic anhydride, itaconic anhydride, etc. Furthermore, the derivative of an acid anhydride of a compound having a group derived from a carboxylic acid is not particularly limited, but examples thereof include acid anhydrides of compounds having a carboxy group such as dimethylmaleic anhydride, diethylmaleic anhydride, diphenylmaleic anhydride, etc., in which at least a part of the hydrogen atoms is substituted with a substituent such as an alkyl group or a phenyl group.
[0104] When a TEMPO oxidation treatment is performed in the carboxyl group introduction step, it is preferable to perform the treatment under conditions of pH 6 or more and 8 or less. Such a treatment is also called a neutral TEMPO oxidation treatment. The neutral TEMPO oxidation treatment can be performed, for example, by adding pulp as a fiber raw material, a nitroxy radical such as TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl) as a catalyst, and sodium hypochlorite as a sacrificial reagent to a sodium phosphate buffer solution (pH = 6.8). By further allowing sodium chlorite to coexist, aldehydes generated during the oxidation process can be efficiently oxidized to carboxyl groups. The TEMPO oxidation treatment may also be performed under conditions of pH 10 or more and 11 or less. Such a treatment is also called an alkaline TEMPO oxidation treatment. The alkaline TEMPO oxidation treatment can be performed, for example, by adding a nitroxy radical such as TEMPO as a catalyst, sodium bromide as a cocatalyst, and sodium hypochlorite as an oxidizing agent to pulp as a fiber raw material.
[0105] The amount of carboxyl groups introduced into the fiber raw material varies depending on the type of the substituent, but for example, when the carboxyl groups are introduced by TEMPO oxidation, the amount is preferably 0.10 mmol / g or more per 1 g (mass) of fine fibrous cellulose, more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 0.90 mmol / g or more. Also, it is preferably 2.5 mmol / g or less, more preferably 2.20 mmol / g or less, and even more preferably 2.00 mmol / g or less. In addition, when the substituent is a carboxymethyl group, it may be 5.8 mmol / g or less per 1 g (mass) of fine fibrous cellulose.
[0106] <Sulfur oxoacid group introduction step> The process for producing fine fibrous cellulose may include, for example, a sulfur oxoacid group introduction step as an ionic substituent introduction step, in which a hydroxyl group in a fiber raw material containing cellulose reacts with a sulfur oxoacid to obtain cellulose fibers having sulfur oxoacid groups (sulfur oxoacid group-introduced fibers).
[0107] In the sulfur oxo acid group introduction step, instead of compound A in the above-mentioned <phosphorus oxo acid group introduction step>, at least one compound (hereinafter also referred to as "compound C") selected from compounds capable of introducing sulfur oxo acid groups by reacting with hydroxyl groups of fiber raw materials containing cellulose is used. Compound C may be any compound having a sulfur atom and capable of forming an ester bond with cellulose, and may include, but is not limited to, sulfuric acid or a salt thereof, sulfurous acid or a salt thereof, and sulfuric acid amide. As sulfuric acid, sulfuric acid of various purities may be used, for example, 96% sulfuric acid (concentrated sulfuric acid). As sulfurous acid, 5% sulfurous acid water may be used. As sulfates or sulfites, lithium salts, sodium salts, potassium salts, ammonium salts of sulfates or sulfites may be used, and these may have various degrees of neutralization. As sulfuric acid amides, sulfamic acid or the like may be used. In the sulfur oxo acid group introduction step, it is preferable to use compound B in the above-mentioned <phosphorus oxo acid group introduction step> in the same manner.
[0108] In the sulfur oxoacid group introduction step, it is preferable to mix the cellulose raw material with an aqueous solution containing sulfur oxoacid and urea and / or a urea derivative, and then heat-treat the cellulose raw material. It is preferable to select a heat-treatment temperature that allows efficient introduction of sulfur oxoacid groups while suppressing thermal decomposition and hydrolysis of the fibers. The heat-treatment temperature is preferably 100°C or higher, more preferably 120°C or higher, and even more preferably 150°C or higher. The heat-treatment temperature is preferably 300°C or lower, more preferably 250°C or lower, and even more preferably 200°C or lower.
[0109] In the heat treatment step, it is preferable to heat until substantially no moisture is present. For this reason, the heat treatment time varies depending on the amount of moisture contained in the cellulose raw material and the amount of the aqueous solution containing sulfur oxoacid and urea and / or a urea derivative added, but is preferably, for example, 10 seconds or more and 10,000 seconds or less. For the heat treatment, various devices having a heat medium can be used, such as a hot air dryer, a stirring dryer, a rotary dryer, a disk dryer, a roll type heater, a plate type heater, a fluidized bed dryer, a band type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far infrared heater, a microwave heater, and a high frequency dryer.
[0110] The amount of sulfur oxoacid groups introduced into the cellulose raw material is preferably 0.10 mmol / g or more, more preferably 0.20 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 1.00 mmol / g or more. The amount of sulfur oxoacid groups introduced into the cellulose raw material is preferably 5.00 mmol / g or less, more preferably 3.00 mmol / g or less. By setting the amount of sulfur oxoacid groups introduced within the above range, it is possible to easily refine the fiber raw material and to increase the stability of the fibrous cellulose.
[0111] <Oxidation with chlorine-based oxidizing agents> The process for producing fine fibrous cellulose may include, for example, an oxidation step using a chlorine-based oxidizing agent as a step for introducing an ionic substituent. In the oxidation step using a chlorine-based oxidizing agent, the chlorine-based oxidizing agent is added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a carboxyl group into the fiber raw material.
[0112] Examples of chlorine-based oxidizing agents include hypochlorous acid, hypochlorites, chlorous acid, chlorites, chloric acid, chlorates, perchloric acid, perchlorates, chlorine dioxide, etc. From the viewpoints of the efficiency of introducing a substituent, and therefore the defibration efficiency, cost, and ease of handling, sodium hypochlorite, sodium chlorite, and chlorine dioxide are preferred.
[0113] The chlorine-based oxidizing agent may be added to the fiber raw material as it is, or may be dissolved in a suitable solvent and then added.
[0114] The reaction temperature in the oxidation step using a chlorine-based oxidizing agent is, for example, preferably 10°C or higher and 100°C or lower, more preferably 15°C or higher and 80°C or lower, and even more preferably 20°C or higher and 60°C or lower.
[0115] The concentration of the chlorine-based oxidizing agent in the solution in the oxidation step using the chlorine-based oxidizing agent is, for example, preferably 1% by mass to 1000% by mass in terms of effective chlorine concentration, more preferably 5% by mass to 500% by mass inclusive, and even more preferably 10% by mass to 100% by mass inclusive. The amount of the chlorine-based oxidizing agent added to the fiber raw material is preferably 1% by mass to 100,000% by mass inclusive, more preferably 10% by mass to 10,000% by mass inclusive, and even more preferably 100% by mass to 5,000% by mass inclusive.
[0116] The reaction time with the chlorine-based oxidizing agent in the oxidation step using the chlorine-based oxidizing agent may vary depending on the reaction temperature, but is preferably from 1 minute to 1000 minutes, more preferably from 10 minutes to 500 minutes, and even more preferably from 20 minutes to 400 minutes. The pH during the reaction is preferably from 5 to 15, more preferably from 7 to 14, and even more preferably from 9 to 13. At the start of the reaction, the pH during the reaction is preferably kept constant (for example, pH 11) by appropriately adding hydrochloric acid or sodium hydroxide. After the reaction, excess reaction reagents, by-products, etc. may be washed with water and removed by filtration or the like.
[0117] <Xanthate formation (xanthogen acid esterification)> The manufacturing process of fine fibrous cellulose may include, for example, a xanthation process as an ionic substituent introduction process. In the xanthation process, carbon disulfide and an alkali compound are added to a wet or dry fiber raw material having a hydroxyl group to react with each other, thereby introducing a xanthate group into the fiber raw material. Specifically, carbon disulfide is added to a fiber raw material that has been converted into alkali cellulose by the method described below, and the reaction is carried out.
[0118] <Alkaline cellulose> When introducing ionic functional groups into the fiber raw material, it is preferable to apply an alkaline solution to the cellulose contained in the fiber raw material to convert the cellulose into alkali cellulose. This treatment causes some of the hydroxyl groups of the cellulose to be ionized, thereby increasing the nucleophilicity (reactivity). The alkaline compound contained in the alkaline solution is not particularly limited, and may be an inorganic alkaline compound or an organic alkaline compound. Because of their high versatility, it is preferable to use, for example, sodium hydroxide, potassium hydroxide, tetraethylammonium hydroxide, or tetrabutylammonium hydroxide. The conversion into alkali cellulose may be performed simultaneously with the introduction of ionic functional groups, may be performed prior to the introduction, or may be performed at both the same timing.
[0119] The solution temperature at the start of alkali cellulose formation is preferably 0°C or higher and 50°C or lower, more preferably 5°C or higher and 40°C or lower, and even more preferably 10°C or higher and 30°C or lower.
[0120] The concentration of the alkaline solution is preferably 0.01 mol / L to 4 mol / L in molar concentration, more preferably 0.1 mol / L to 3 mol / L in molar concentration, and even more preferably 1 mol / L to 2.5 mol / L in molar concentration. In particular, when the treatment temperature is less than 10° C., the concentration is preferably 1 mol / L to 2 mol / L in molar concentration.
[0121] The treatment time for alkali cellulose formation is preferably 1 minute or more, more preferably 10 minutes or more, and even more preferably 30 minutes or more, and the alkali treatment time is preferably 6 hours or less, more preferably 5 hours or less, and even more preferably 4 hours or less.
[0122] By adjusting the type of alkaline solution, treatment temperature, concentration, and immersion time as described above, it is possible to suppress the penetration of the alkaline solution into the crystalline regions of cellulose, making it easier to maintain the crystal structure of cellulose type I, and increasing the yield of fine fibrous cellulose.
[0123] When the introduction of ionic functional groups and the conversion to alkali cellulose are not performed simultaneously, the alkali cellulose obtained by the alkali treatment is preferably subjected to solid-liquid separation and water removal by a general deliquoring method such as centrifugation or filtration. This improves the reaction efficiency in the subsequent ionic functional group introduction step. The cellulose fiber concentration after solid-liquid separation is preferably 5% to 50%, more preferably 10% to 40%, and even more preferably 15% to 35%.
[0124] <Phosphoalkylation> The process for producing fine fibrous cellulose may include, for example, a phosphoalkylation process as an ionic substituent introduction process. In the phosphoalkylation process, a compound having a reactive group and a phospho group or a phosphine group (compound E A ), an optional alkaline compound, the aforementioned compound B selected from urea and its derivatives, and compound C as a reaction aid are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a phosphonic group or a phosphine group into the fiber raw material.
[0125] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group).
[0126] Compound E A Examples of the vinyl phosphate include vinyl phosphoric acid, phenyl vinyl phosphonic acid, phenyl vinyl phosphinic acid, etc. Vinyl phosphoric acid is preferred from the viewpoints of the efficiency of introducing a substituent, and therefore the defibration efficiency, cost, and ease of handling.
[0127] Furthermore, as an optional component, it is also preferable to use the compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner, and it is also possible to further add C. The amount of addition is also preferably as described above.
[0128] Compound E AThe reagent may be added to the fiber raw material as it is, or may be dissolved in a suitable solvent and added. The fiber raw material is preferably converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0129] The temperature during the reaction is, for example, preferably from 50°C to 300°C, more preferably from 100°C to 250°C, and even more preferably from 130°C to 200°C.
[0130] Compound E A The amount of the additive to the fiber raw material is preferably from 1% by mass to 100,000% by mass, more preferably from 2% by mass to 10,000% by mass, and even more preferably from 5% by mass to 1,000% by mass.
[0131] The reaction time may vary depending on the reaction temperature, but is preferably from 1 to 1000 minutes, more preferably from 10 to 500 minutes, and even more preferably from 20 to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0132] <Sulfoalkylation> The process for producing fine fibrous cellulose may include, for example, a sulfoalkylation process as a process for introducing an ionic substituent. In the sulfoalkylation, a compound having a reactive group and a sulfone group (compound E) is used as an essential component. B ) as an optional component, an alkaline compound, the above-mentioned compound B selected from urea and its derivatives, and compound C as a reaction aid are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a sulfone group into the fiber raw material.
[0133] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group).
[0134] Compound E BExamples of such sulfonates include sodium 2-chloroethanesulfonate, sodium vinylsulfonate, sodium p-styrenesulfonate, 2-acrylamido-2-methylpropanesulfonic acid, etc. Among these, sodium vinylsulfonate is preferred from the standpoint of the efficiency of introducing a substituent, and therefore the defibration efficiency, cost, and ease of handling.
[0135] Furthermore, as an optional component, it is also preferable to use the compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner, and it is also possible to further add C. The amount of addition is also preferably as described above.
[0136] Compound E B The reagent may be added to the fiber raw material as it is, or may be dissolved in a suitable solvent and added. The fiber raw material is preferably converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0137] The temperature during the reaction is, for example, preferably from 50°C to 300°C, more preferably from 100°C to 250°C, and even more preferably from 130°C to 200°C.
[0138] Compound E B The amount of the additive to the fiber raw material is preferably from 1% by mass to 100,000% by mass, more preferably from 2% by mass to 10,000% by mass, and even more preferably from 5% by mass to 1,000% by mass.
[0139] The reaction time may vary depending on the reaction temperature, but is preferably, for example, from 1 minute to 1000 minutes, more preferably from 10 minutes to 500 minutes, and even more preferably from 20 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0140] <Carboxyalkylation> The process for producing fine fibrous cellulose may include, for example, a carboxyalkylation step as an ionic substituent introduction step. C ), an optional alkaline compound, the aforementioned compound B selected from urea and its derivatives, and compound C as a reaction aid are added to a wet or dry fiber raw material having a hydroxyl group and reacted to introduce a carboxyl group into the fiber raw material.
[0141] Examples of the reactive group include a halogenated alkyl group, a vinyl group, and an epoxy group (glycidyl group).
[0142] Compound E C As the chloropropionic acid, monochloroacetic acid, sodium monochloroacetate, 2-chloropropionic acid, and sodium 2-chloropropionate are preferred from the viewpoints of the efficiency of introducing a substituent, and therefore the defibration efficiency, cost, and ease of handling.
[0143] Furthermore, as an optional component, it is also preferable to use the compound B in the above-mentioned <Phosphorus oxo acid group introduction step> in the same manner, and it is also possible to further add C. The amount of addition is also preferably as described above.
[0144] Compound E C The reagent may be added to the fiber raw material as it is, or may be dissolved in a suitable solvent and added. The fiber raw material is preferably converted into alkali cellulose in advance or simultaneously with the reaction. The method of conversion into alkali cellulose is as described above.
[0145] The temperature during the reaction is, for example, preferably from 50°C to 300°C, more preferably from 100°C to 250°C, and even more preferably from 130°C to 200°C.
[0146] Compound E CThe amount of the additive to the fiber raw material is preferably from 1% by mass to 100,000% by mass, more preferably from 2% by mass to 10,000% by mass, and even more preferably from 5% by mass to 1,000% by mass.
[0147] The reaction time may vary depending on the reaction temperature, but is preferably, for example, from 1 minute to 1000 minutes, more preferably from 10 minutes to 500 minutes, and even more preferably from 20 minutes to 400 minutes. After the reaction, excess reaction reagents, by-products, etc. may be washed and removed with water by filtration or the like.
[0148] <Cleaning process> In the method for producing fine fibrous cellulose in this embodiment, a washing step can be carried out on the ionic substituent-introduced fiber as necessary. The washing step is carried out, for example, by washing the ionic substituent-introduced fiber with water or an organic solvent. The washing step may be carried out after each step described below, and the number of washing steps carried out in each washing step is not particularly limited.
[0149] <Alkaline treatment process> When producing fine fibrous cellulose, an alkali treatment may be carried out on the fiber raw material between the step of introducing an ionic substituent and the step of defibrating the fiber, which will be described later. The method of the alkali treatment is not particularly limited, but may be, for example, a method of immersing the fiber having an ionic substituent introduced therein in an alkali solution.
[0150] The alkaline compound contained in the alkaline solution is not particularly limited, and may be an inorganic alkaline compound or an organic alkaline compound. In this embodiment, it is preferable to use, for example, sodium hydroxide or potassium hydroxide as the alkaline compound because of its high versatility. The solvent contained in the alkaline solution may be either water or an organic solvent. Among them, the solvent contained in the alkaline solution is preferably a polar solvent including water or a polar organic solvent exemplified by alcohol, and more preferably an aqueous solvent including at least water. As the alkaline solution, for example, an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution is preferable because of its high versatility.
[0151] The temperature of the alkaline solution in the alkaline treatment step is not particularly limited, but is preferably 5°C to 80°C, and more preferably 10°C to 60°C. The immersion time of the ionic substituent-introduced fiber in the alkaline solution in the alkaline treatment step is not particularly limited, but is preferably 5 minutes to 30 minutes, and more preferably 10 minutes to 20 minutes. The amount of the alkaline solution used in the alkaline treatment is not particularly limited, but is preferably 100 mass% to 100000 mass%, and more preferably 1000 mass% to 10000 mass%, based on the absolute dry mass of the ionic substituent-introduced fiber. When the fibrous cellulose has anionic groups, the alkaline treatment may include neutralization and / or ion exchange of the anionic groups. In this case, the temperature of the alkaline solution is preferably room temperature.
[0152] In order to reduce the amount of alkaline solution used in the alkaline treatment step, the ionic substituent-introduced fiber may be washed with water or an organic solvent after the ionic substituent-introducing step and before the alkaline treatment step. From the viewpoint of improving handleability, it is preferable to wash the alkaline-treated ionic substituent-introduced fiber with water or an organic solvent after the alkaline treatment step and before the defibration treatment step.
[0153] <Acid treatment process> When producing fine fibrous cellulose, the fiber raw material may be subjected to an acid treatment between the step of introducing an ionic substituent and the defibration treatment step described later. For example, the step of introducing an ionic substituent, the acid treatment, the alkali treatment, and the defibration treatment may be performed in this order.
[0154] The method of acid treatment is not particularly limited, but may be, for example, a method of immersing the fiber raw material in an acidic solution containing an acid. The concentration of the acidic solution used is not particularly limited, but is preferably, for example, 10% by mass or less, and more preferably, 5% by mass or less. The pH of the acidic solution used is not particularly limited, but is preferably, for example, 0 to 4, and more preferably, 1 to 3. The acid contained in the acidic solution may be, for example, an inorganic acid, a sulfonic acid, a carboxylic acid, or the like. Examples of inorganic acids include sulfuric acid, nitric acid, hydrobromic acid, hydroiodic acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, phosphoric acid, and boric acid. Examples of sulfonic acids include, for example, methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid. Examples of carboxylic acids include, for example, formic acid, acetic acid, citric acid, gluconic acid, lactic acid, oxalic acid, and tartaric acid. Among these, it is particularly preferable to use hydrochloric acid or sulfuric acid.
[0155] The temperature of the acid solution in the acid treatment is not particularly limited, but is preferably, for example, 5°C to 100°C, and more preferably, 20°C to 90°C. The immersion time in the acid solution in the acid treatment is not particularly limited, but is, for example, preferably, 5 minutes to 120 minutes, and more preferably, 10 minutes to 60 minutes. The amount of the acid solution used in the acid treatment is not particularly limited, but is, for example, preferably, 100 mass% to 100,000 mass%, and more preferably, 1000 mass% to 10,000 mass%, based on the absolute dry mass of the fiber raw material. When the fine fibrous cellulose has cationic groups, the acid treatment may include neutralization and / or ion exchange of the cationic groups. In this case, the temperature of the acid solution is preferably room temperature.
[0156] <Defibrillation processing> The ionic substituent-introduced fibers are defibrated in a defibration process to obtain fine fibrous cellulose. In the defibration process, for example, a defibration treatment device can be used. The defibration treatment device is not particularly limited, but for example, a high-speed defibrator, a grinder (stone mill type grinder), a high-pressure homogenizer or an ultra-high-pressure homogenizer, a high-pressure collision type grinder, a ball mill, a bead mill, a disk type refiner, a conical refiner, a biaxial kneader, a vibration mill, a homomixer under high-speed rotation, an ultrasonic disperser, or a beater can be used. Among the above defibration treatment devices, it is more preferable to use a high-speed defibrator, a high-pressure homogenizer, or an ultra-high-pressure homogenizer, which are less affected by the grinding media and have less risk of contamination.
[0157] In the defibration process, for example, it is preferable to dilute the ionic substituent-introduced fiber with a dispersion medium to make it into a slurry state. As the dispersion medium, one or more selected from water and organic solvents such as polar organic solvents can be used. The polar organic solvent is not particularly limited, but for example, alcohols, polyhydric alcohols, ketones, ethers, esters, aprotic polar solvents, etc. are preferable. Examples of alcohols include methanol, ethanol, isopropanol, n-butanol, isobutyl alcohol, etc. Examples of polyhydric alcohols include ethylene glycol, propylene glycol, glycerin, etc. Examples of ketones include acetone, methyl ethyl ketone (MEK), etc. Examples of ethers include diethyl ether, tetrahydrofuran, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono n-butyl ether, propylene glycol monomethyl ether, etc. Examples of esters include ethyl acetate, butyl acetate, etc. Aprotic polar solvents include dimethylsulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAc), and N-methyl-2-pyrrolidinone (NMP).
[0158] The solid content concentration of the fine fibrous cellulose during the defibration treatment can be appropriately set. In addition, the slurry obtained by dispersing the ionic substituent-introduced fibers in a dispersion medium may contain solids other than the ionic substituent-introduced fibers, such as urea having hydrogen bonding properties.
[0159] <Optional ingredients> The fiber layer may contain any component other than the fine fibrous cellulose. Examples of the optional component include hydrophilic polymers, hydrophilic low molecules, organic ions, etc. Among them, the fiber layer is preferably a layer further containing a hydrophilic polymer.
[0160] The hydrophilic polymer is preferably a hydrophilic oxygen-containing organic compound (excluding the above-mentioned cellulose fiber). In this case, it is particularly preferable that the oxygen-containing organic compound is a hydrophilic organic compound. The hydrophilic oxygen-containing organic compound can improve the strength, density, chemical resistance, etc. of the fiber layer. The hydrophilic oxygen-containing organic compound preferably has an SP value of 9.0 or more. In addition, it is preferable that the hydrophilic oxygen-containing organic compound is one in which 1 g or more of the oxygen-containing organic compound dissolves in 100 ml of ion-exchanged water.
[0161] Examples of hydrophilic polymers include polyethylene glycol, polyethylene oxide, casein, dextrin, starch, modified starch, polyvinyl alcohol, modified polyvinyl alcohol (acetoacetylated polyvinyl alcohol, etc.), polyethylene oxide, polyvinylpyrrolidone, polyvinyl methyl ether, polyacrylates, polyacrylamide, acrylic acid alkyl ester copolymers, urethane copolymers, cellulose derivatives (hydroxyethyl cellulose, carboxyethyl cellulose, carboxymethyl cellulose, etc.), etc. Among these, from the viewpoint of improving the strength, density, chemical resistance, etc. of the fiber layer, the hydrophilic polymer is preferably at least one selected from the group consisting of polyethylene glycol, polyethylene oxide, and polyvinyl alcohol, and particularly preferably polyvinyl alcohol.
[0162] When polyvinyl alcohol is blended in the fiber layer, the saponification degree of the polyvinyl alcohol is preferably 99.9% or less, more preferably 99% or less, and even more preferably 95% or less. The saponification degree of the polyvinyl alcohol is preferably 85% or more. By incorporating polyvinyl alcohol having a saponification degree within the above range in the fiber layer, the transparency of the fiber layer can be more effectively increased, and as a result, a sheet with higher transparency can be obtained.
[0163] The weight-average molecular weight of the hydrophilic polymer may be 10,000 or more, preferably 50,000 or more, and more preferably 100,000 or more. The weight-average molecular weight of the hydrophilic polymer is preferably 8 million or less, and more preferably 5 million or less.
[0164] The content of the hydrophilic polymer is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and particularly preferably 20% by mass or more, based on the total mass of the fiber layer. The content of the hydrophilic polymer is preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 80% by mass or less, based on the total mass of the fiber layer. By setting the content of the hydrophilic polymer within the above range, a sheet having high strength and high transparency can be formed.
[0165] Examples of hydrophilic low molecular weight compounds include glycerin, sorbitol, and ethylene glycol. Examples of organic ions include tetraalkylammonium ions and tetraalkylphosphonium ions. Examples of tetraalkylammonium ions include tetramethylammonium ions, tetraethylammonium ions, tetrapropylammonium ions, tetrabutylammonium ions, tetrapentylammonium ions, tetrahexylammonium ions, tetraheptylammonium ions, tributylmethylammonium ions, lauryltrimethylammonium ions, cetyltrimethylammonium ions, stearyltrimethylammonium ions, octyldimethylethylammonium ions, lauryldimethylethylammonium ions, didecyldimethylammonium ions, lauryldimethylbenzylammonium ions, and tributylbenzylammonium ions. Examples of tetraalkylphosphonium ions include tetramethylphosphonium ions, tetraethylphosphonium ions, tetrapropylphosphonium ions, tetrabutylphosphonium ions, and lauryltrimethylphosphonium ions. Examples of tetrapropylonium ions and tetrabutylonium ions include tetra-n-propylonium ions and tetra-n-butylonium ions, respectively.
[0166] <Surface treatment> The surface of the fiber layer facing the resin layer may be subjected to a surface treatment. Examples of the surface treatment method include corona treatment, plasma discharge treatment, UV irradiation treatment, electron beam irradiation treatment, and flame treatment. Among them, the surface treatment is preferably at least one selected from corona treatment and plasma discharge treatment. The plasma discharge treatment is preferably vacuum plasma discharge treatment.
[0167] (Sheet manufacturing method) The method for producing the sheet includes a step of forming a resin layer on both sides of a fiber layer containing fibrous cellulose having a fiber width of 1000 nm or less, and the surface roughness (Ra) of both sides of the sheet produced in this manner is 12.0 nm or less.
[0168] The step of forming resin layers on both sides of the fiber layer may be a step of laminating a resin film or a resin sheet on both sides of the fiber layer, but is preferably a step of forming resin layers by applying a resin coating liquid to both sides of the fiber layer. Here, the resin coating liquid preferably contains a solvent, and the resin layers formed on both sides of the fiber layer are preferably solvent-coated layers.
[0169] The viscosity of the resin coating liquid containing the solvent is preferably 100 cps or less, more preferably 80 cps or less, and even more preferably 60 cps or less. Here, the viscosity of the resin coating liquid is a value measured by a B-type viscometer. The measurement conditions are a rotation speed of 60 rpm, and the viscosity value 1 minute after the start of measurement is taken as the viscosity of the resin coating liquid. As the B-type viscometer, for example, an analog viscometer T-LVT manufactured by BLOOKFIELD Corporation can be used. By setting the viscosity of the resin coating liquid within the above range, it becomes easier to control the surface roughness of the sheet within a predetermined range, and as a result, the transparency of the sheet can be more effectively increased.
[0170] The solid content in the resin coating liquid is preferably 12% by mass or less, more preferably 10% by mass or less, and even more preferably 8% by mass or less. Here, the solid content in the resin coating liquid is mainly the content of the resin components contained in the resin coating liquid, but when the resin coating liquid contains optional components such as an adhesion aid as described below, the content of the optional components is also included.
[0171] The resin coating liquid may contain optional components such as an adhesion aid, if necessary. Preferred examples of the adhesion aid include the adhesion aids described above.
[0172] The step of forming a resin layer by applying a resin coating liquid to both sides of the fiber layer can be carried out using a known coating device. Examples of the coating device include a blade coater, an air knife coater, a roll coater, a bar coater, a gravure coater, a microgravure coater, a rod blade coater, a lip coater, a die coater, and a curtain coater. In this case, it is preferable to apply the resin coating liquid so that a resin layer having a thickness of 10 μm or less is formed on both sides of the fiber layer.
[0173] The method for producing the sheet preferably includes a step of forming a fiber layer containing fibrous cellulose having a fiber width of 1000 nm or less as a pre-step of the step of forming a resin layer on both sides of the fiber layer. Here, the step of forming the fiber layer includes a step of obtaining a fibrous cellulose-containing composition (hereinafter also referred to as a slurry or coating liquid) having a fiber width of 1000 nm or less, and a coating step of coating the fibrous cellulose-containing composition on a substrate, or a papermaking step of making the fibrous cellulose-containing composition. This results in the above-mentioned fiber layer being obtained. The fibrous cellulose-containing composition is preferably a composition containing a hydrophilic polymer as described above.
[0174] <Coating process> In the coating process, for example, a fibrous cellulose-containing composition (slurry) containing fibrous cellulose is coated on a substrate, and the resulting fiber sheet is dried and peeled off from the substrate to obtain a fiber layer. In addition, by using a coating device and a long substrate, the fiber sheet that will become the fiber layer can be continuously produced.
[0175] The material of the substrate used in the coating process is not particularly limited, but a substrate with high wettability to the fibrous cellulose-containing composition (slurry) is better in that it can suppress shrinkage of the fiber sheet during drying, but it is preferable to select a substrate from which the fiber sheet formed after drying can be easily peeled off. Among them, resin films and plates or metal films and plates are preferred, but are not particularly limited. For example, resin films and plates such as polypropylene, acrylic, polyethylene terephthalate, vinyl chloride, polystyrene, polycarbonate, and polyvinylidene chloride, metal films and plates such as aluminum, zinc, copper, and iron plates, and those whose surfaces have been oxidized, stainless steel films and plates, and brass films and plates, etc. can be used.
[0176] In the coating process, if the viscosity of the slurry is low and the slurry spreads on the substrate, a damming frame may be fixed on the substrate to obtain a fiber sheet of a predetermined thickness and basis weight. The damming frame is not particularly limited, but it is preferable to select a frame that allows the end of the fiber sheet to be easily peeled off after drying. From this viewpoint, a molded resin plate or metal plate is more preferable. In this embodiment, for example, resin plates such as polypropylene plates, acrylic plates, polyethylene terephthalate plates, vinyl chloride plates, polystyrene plates, polycarbonate plates, and polyvinylidene chloride plates, metal plates such as aluminum plates, zinc plates, copper plates, and iron plates, and plates whose surfaces have been oxidized, stainless steel plates, brass plates, and the like can be used. The coating machine for coating the substrate with the slurry is not particularly limited, and examples thereof include a roll coater, a gravure coater, a die coater, a curtain coater, an air doctor coater, etc. Since the thickness of the fiber sheet can be made more uniform, a die coater, a curtain coater, and a spray coater are particularly preferred.
[0177] The slurry temperature and the ambient temperature when the slurry is applied to the substrate are not particularly limited, but are preferably, for example, 5°C to 80°C, more preferably 10°C to 60°C, even more preferably 15°C to 50°C, and particularly preferably 20°C to 40°C. If the application temperature is equal to or higher than the lower limit, the slurry can be applied more easily. If the application temperature is equal to or lower than the upper limit, the evaporation of the dispersion medium during application can be suppressed.
[0178] In the coating process, the finished basis weight of the fiber sheet is preferably 10 g / m 2 More than 100g / m 2 More preferably, 20 g / m 2 More than 60g / m 2 It is preferable to coat the slurry on the substrate so that the basis weight falls within the above range. By coating the slurry so that the basis weight falls within the above range, a fiber sheet having superior strength can be obtained.
[0179] As described above, the coating step includes a step of drying the slurry coated on the substrate. The step of drying the slurry is not particularly limited, but may be performed, for example, by a non-contact drying method, a method of drying while restraining the fiber sheet, or a combination of these.
[0180] The non-contact drying method is not particularly limited, but for example, a method of drying by heating with hot air, infrared rays, far infrared rays, or near infrared rays (heat drying method), or a method of drying by vacuum (vacuum drying method) can be applied. The heat drying method and the vacuum drying method may be combined, but the heat drying method is usually applied. Drying by infrared rays, far infrared rays, or near infrared rays can be performed using, for example, an infrared device, a far infrared device, or a near infrared device, but is not particularly limited.
[0181] The heating temperature in the heat drying method is not particularly limited, but is preferably 20°C to 150°C, more preferably 25°C to 105°C. If the heating temperature is equal to or higher than the lower limit, the dispersion medium can be quickly evaporated. If the heating temperature is equal to or lower than the upper limit, the cost required for heating can be reduced and discoloration of the fibrous cellulose due to heat can be suppressed.
[0182] <Paper making process> The papermaking process is carried out by making the slurry into paper using a papermaking machine. The papermaking machine used in the papermaking process is not particularly limited, but may be, for example, a continuous papermaking machine such as a fourdrinier type, a cylinder type, or an inclined type, or a multi-layer papermaking machine that combines these. In the papermaking process, a known papermaking method such as handmaking may be used.
[0183] The papermaking process is carried out by filtering the slurry with a wire, dehydrating the slurry to obtain a fiber sheet in a wet paper state, and then pressing and drying the fiber sheet. The filter cloth used for filtering and dehydrating the slurry is not particularly limited, but it is more preferable that, for example, fibrous cellulose does not pass through and the filtration speed is not too slow. Such a filter cloth is not particularly limited, but for example, a fiber sheet, woven fabric, or porous membrane made of an organic polymer is preferable. The organic polymer is not particularly limited, but for example, a non-cellulose organic polymer such as polyethylene terephthalate, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), etc. In this embodiment, for example, a polytetrafluoroethylene porous membrane with a pore size of 0.1 μm to 20 μm, polyethylene terephthalate with a pore size of 0.1 μm to 20 μm, or polyethylene woven fabric, etc., are mentioned.
[0184] A method for producing a fiber sheet from a slurry can be carried out, for example, by using a production apparatus including a water squeezing section in which a slurry containing fibrous cellulose is discharged onto an endless belt and the dispersion medium is squeezed out of the discharged slurry to produce a web, and a drying section in which the web is dried to produce a fiber sheet. An endless belt is disposed between the water squeezing section and the drying section, and the web produced in the water squeezing section is transported to the drying section while still placed on the endless belt.
[0185] The dehydration method used in the papermaking process is not particularly limited, but may be, for example, a dehydration method commonly used in paper manufacturing. Among these, a method of dehydrating using a fourdrinier, cylinder, or inclined wire, followed by further dehydration using a roll press, is preferred. Furthermore, the drying method used in the papermaking process is not particularly limited, but may be, for example, a method used in paper manufacturing. Among these, a drying method using a cylinder dryer, Yankee dryer, hot air drying, near-infrared heater, infrared heater, or the like is more preferred.
[0186] (Application) The sheet of the present invention has high transparency and excellent optical properties. From the viewpoint of utilizing the excellent optical properties, the sheet of the present invention is preferably used for optical members. More specifically, the sheet of the present invention is suitable for use as a light-transmitting substrate such as various display devices and various solar cells. The sheet of the present invention is also suitable for use as a substrate for electronic devices, a component for home appliances, a window material for various vehicles and buildings, an interior material, an exterior material, a packaging material, and the like.
[0187] (Laminate) The present invention may also relate to a laminate obtained by laminating another layer on the above-mentioned sheet. For example, in a resin layer / fiber layer / resin layer structure of the sheet, another layer may be laminated on the side of the resin layer that is not in contact with the fiber layer to form a laminate. Examples of the other layer include a cycloolefin polymer film and a polyimide film. EXAMPLES
[0188] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below. In the following, Examples 10, 17 and 18 shall be read as Reference Examples 10, 17 and 18, respectively.
[0189] <Production Example 1> (Phosphated pulp production) The raw pulp used was softwood kraft pulp (solid content 93% by mass, basis weight 208 g / m) manufactured by Oji Paper. 2 A sheet-like pulp (with a Canadian Standard Freeness (CSF) of 700 mL when disintegrated and measured according to JIS P 8121:2012) was used. This raw pulp was subjected to phosphorus oxo-oxidation treatment as follows. First, a mixed aqueous solution of ammonium dihydrogen phosphate and urea was added to 100 parts by mass (bone dry mass) of the raw pulp to prepare 45 parts by mass of ammonium dihydrogen phosphate, 120 parts by mass of urea, and 150 parts by mass of water, thereby obtaining a chemical-impregnated pulp. Next, the obtained chemical-impregnated pulp was heated in a hot air dryer at 165°C for 200 seconds to introduce phosphoric acid groups into the cellulose in the pulp, thereby obtaining a phosphorylated pulp.
[0190] The phosphorylated pulp was then washed. The washing was carried out by pouring 10 L of ion-exchanged water into 100 g (bone dry weight) of phosphorylated pulp to obtain a pulp dispersion, stirring the pulp to uniformly disperse it, and then repeatedly filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate reached 100 μS / cm or less.
[0191] Next, the washed phosphorylated pulp was subjected to an alkali treatment (neutralization treatment) as follows: First, the washed phosphorylated pulp was diluted with 10 L of ion-exchanged water, and then a 1N aqueous sodium hydroxide solution was added little by little while stirring to obtain a phosphorylated pulp slurry having a pH of 12 to 13. Next, the phosphorylated pulp slurry was dehydrated to obtain phosphorylated pulp that had been subjected to an alkali treatment (neutralization treatment).
[0192] Next, the neutralized phosphorylated pulp was subjected to the above-mentioned washing treatment. The infrared absorption spectrum of the phosphorylated pulp thus obtained was measured using FT-IR. -1 Absorption due to the P=O of the phosphate group was observed near the nucleus, confirming that the phosphate group had been added to the pulp. In addition, when the obtained phosphorylated pulp was analyzed using an X-ray diffractometer, typical peaks were confirmed at two positions, near 2θ=14° to 17° and near 2θ=22° to 23°, confirming that it had cellulose type I crystals.
[0193] (Defibrillation process) Ion-exchanged water was added to the obtained phosphorylated pulp to prepare a slurry with a solid content of 2% by mass. This slurry was treated four times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion (A) containing fine fibrous cellulose.
[0194] X-ray diffraction confirmed that the fine fibrous cellulose maintained cellulose type I crystals. The fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3 to 5 nm. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the method for measuring the amount of phosphorus oxoacid groups described below was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.
[0195] <Production Example 2> (Production of Phosphosphite Pulp) A phosphited pulp was obtained by carrying out the same operation as in Production Example 1, except that 33 parts by mass of phosphorous acid (phosphonic acid) was used instead of ammonium dihydrogen phosphate.
[0196] The infrared absorption spectrum of the phosphorous pulp obtained was measured using FT-IR. -1 Absorption due to the P=O of the phosphonic acid group, which is a tautomer of the phosphorous acid group, was observed near the nucleus, confirming that the phosphorous acid group (phosphonic acid group) was added to the pulp. In addition, when the obtained phosphorous-containing pulp was analyzed using an X-ray diffraction device, typical peaks were confirmed at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°, confirming that it has cellulose type I crystals.
[0197] (Defibrillation process) Ion-exchanged water was added to the obtained phosphorous-substituted pulp to prepare a slurry having a solid content concentration of 2% by mass. This slurry was treated four times at a pressure of 200 MPa with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a fine fibrous cellulose dispersion (B) containing fine fibrous cellulose. X-ray diffraction confirmed that this fine fibrous cellulose maintained cellulose I type crystals. In addition, the fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3 to 5 nm. The amount of phosphorous groups (amount of first dissociated acid) measured by the method for measuring the amount of phosphorous oxo acid groups described below was 1.51 mmol / g. The total amount of dissociated acid was 1.54 mmol / g.
[0198] <Production Example 3> (Production of TEMPO oxidized pulp) As the raw material pulp, softwood kraft pulp (undried) manufactured by Oji Paper Co., Ltd. was used. This raw material pulp was subjected to an alkaline TEMPO oxidation treatment as follows. First, the raw material pulp equivalent to 100 parts by mass of dry mass, 1.6 parts by mass of TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl), and 10 parts by mass of sodium bromide were dispersed in 10,000 parts by mass of water. Next, a 13% by mass aqueous solution of sodium hypochlorite was added to 3.8 mmol per 1.0 g of pulp to start the reaction. During the reaction, a 0.5 M aqueous solution of sodium hydroxide was added dropwise to keep the pH at 10 to 10.5, and the reaction was deemed to be complete when no change in pH was observed.
[0199] The TEMPO oxidized pulp was then washed. The washing was performed by dehydrating the pulp slurry after TEMPO oxidation to obtain a dehydrated sheet, pouring 5,000 parts by mass of ion-exchanged water into the sheet, stirring to disperse the sheet uniformly, and then filtering and dehydrating the sheet. The washing was completed when the electrical conductivity of the filtrate reached 100 μS / cm or less.
[0200] The amount of carboxyl groups in the TEMPO oxidized pulp obtained was 1.30 mmol / g, as measured by the method described below. When the obtained TEMPO oxidized pulp was analyzed using an X-ray diffractometer, typical peaks were confirmed at two positions, around 2θ = 14° to 17° and around 2θ = 22° to 23°, and it was confirmed that the pulp contained cellulose type I crystals.
[0201] (Defibrillation process) Ion-exchanged water was added to the obtained TEMPO oxidized pulp to prepare a slurry with a solid content concentration of 2% by mass. This slurry was treated four times at a pressure of 200 MPa with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a fine fibrous cellulose dispersion (C) containing fine fibrous cellulose. X-ray diffraction confirmed that this fine fibrous cellulose maintained cellulose I type crystals. In addition, the fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3 to 5 nm. The amount of carboxyl groups measured by the method for measuring the amount of carboxyl groups described below was 1.30 mmol / g.
[0202] <Production Example 4> (Manufacture of sulfated pulp) Except for using 38 parts by mass of amidosulfuric acid instead of ammonium dihydrogen phosphate, the same operation as in Production Example 1 was carried out to obtain sulfated pulp, except that the heating time in the hot air dryer was 20 minutes.
[0203] The infrared absorption spectrum of the sulfated pulp obtained was measured using FT-IR. -1 Absorption due to sulfate groups was observed in the vicinity, confirming that sulfate groups had been added to the pulp.
[0204] (Defibrillation process) Ion-exchanged water was added to the obtained sulfated pulp, and the mixture was stirred to prepare a 2% by mass slurry. This slurry was treated four times at a pressure of 200 MPa using a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a fine fibrous cellulose dispersion (D) containing fine fibrous cellulose. X-ray diffraction confirmed that the fine fibrous cellulose maintained cellulose type I crystals. The fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 2 to 5 nm. The amount of sulfate groups measured by the method for measuring the amount of sulfur oxoacid groups described below was 1.47 mmol / g.
[0205] <Measurement> (Measurement of phosphorus oxoacid group content) The amount of phosphorus oxoacid groups in the fine fibrous cellulose (equivalent to the amount of phosphorus oxoacid groups in the phosphorus oxo-oxidized pulp) was measured by adding ion exchange water to a fine fibrous cellulose dispersion containing the target fine fibrous cellulose to adjust the content to 0.2 mass%, treating the dispersion with ion exchange resin, and then titrating the dispersion with alkali. Treatment with ion exchange resin was carried out by adding 1 / 10 by volume of a strongly acidic ion exchange resin (Amberjet 1024; manufactured by Organo Corporation, conditioned) to the above-mentioned fine fibrous cellulose-containing slurry, shaking for 1 hour, and then pouring onto a mesh with 90 μm openings to separate the resin and the slurry. The titration using alkali was performed by adding 10 μL of 0.1N sodium hydroxide solution every 5 seconds to the slurry containing fine fibrous cellulose after the treatment with ion exchange resin, and measuring the change in the pH value of the slurry. Nitrogen gas was blown into the slurry 15 minutes before the start of the titration. In this neutralization titration, two points were observed where the increment (the differential value of pH with respect to the amount of alkali added) was maximum on the curve plotting the measured pH against the amount of alkali added. Of these, the first maximum point of the increment obtained after the start of the alkali addition is called the first end point, and the second maximum point of the increment obtained next is called the second end point (Figure 2). The amount of alkali required from the start of the titration to the first end point is equal to the amount of first dissociated acid in the slurry used for the titration. The amount of alkali required from the start of the titration to the second end point is equal to the total amount of dissociated acid in the slurry used for the titration. The amount of alkali (mmol) required from the start of titration to the first end point divided by the solid content (g) in the slurry to be titrated was defined as the amount of phosphorus oxoacid group (first dissociated acid amount) (mmol / g). The amount of alkali (mmol) required from the start of titration to the second end point divided by the solid content (g) in the slurry to be titrated was defined as the total dissociated acid amount (mmol / g).
[0206] (Measurement of Carboxy Group Amount) The amount of carboxyl groups in the fine fibrous cellulose (equivalent to the amount of carboxyl groups in the TEMPO oxidized pulp) was measured by adding ion exchanged water to a fine fibrous cellulose dispersion containing the target fine fibrous cellulose to adjust the content to 0.2 mass%, treating the dispersion with ion exchange resin, and then titrating the dispersion with alkali. Treatment with ion exchange resin was carried out by adding 1 / 10 by volume of a strongly acidic ion exchange resin (Amberjet 1024; manufactured by Organo Corporation, conditioned) to a 0.2% by mass slurry containing fine fibrous cellulose, shaking for 1 hour, and then pouring onto a mesh with 90 μm openings to separate the resin and the slurry. In addition, the titration using an alkali was performed by measuring the change in the pH value of the slurry while adding 0.1N aqueous sodium hydroxide to the fibrous cellulose-containing slurry after the treatment with the ion exchange resin. When the change in pH is observed while adding aqueous sodium hydroxide, a titration curve as shown in FIG. 3 is obtained. As shown in FIG. 3, in this neutralization titration, a point is observed where the increment (differential value of pH with respect to the amount of alkali added) is maximum in the curve plotting the measured pH against the amount of alkali added. This maximum point of the increment is called the first end point. Here, the region from the start of the titration to the first end point in FIG. 3 is called the first region. The amount of alkali required in the first region is equal to the amount of carboxyl groups in the slurry used for the titration. The amount of alkali required in the first region of the titration curve (mmol) was divided by the solid content (g) in the fine fibrous cellulose-containing slurry to be titrated to calculate the amount of carboxyl groups introduced (mmol / g). The amount of carboxyl groups introduced (mmol / g) is calculated assuming that the counter ion of the carboxyl group is a hydrogen ion (H + ) (hereinafter referred to as the amount of carboxy groups (acid type)) per gram of mass of fibrous cellulose.
[0207] (Measurement of sulfur oxoacid group content) The obtained fibrous cellulose was wet ashed using perchloric acid and concentrated nitric acid, then appropriately diluted and the amount of sulfur was measured by ICP emission spectrometry. The amount of sulfur was divided by the bone dry mass of the fibrous cellulose used to measure the amount of sulfate groups (unit: mmol / g).
[0208] <Example 1> (Dissolution of polyvinyl alcohol) Ion-exchanged water was mixed with acetoacetyl-modified polyvinyl alcohol (Gohsenex, manufactured by Mitsubishi Chemical Corporation). TM Z-200) was added to a concentration of 12% by mass, and the mixture was stirred at 95° C. for 1 hour to dissolve. By the above procedure, an aqueous polyvinyl alcohol solution (A) was obtained.
[0209] (Formation of fiber layer) The fine fibrous cellulose dispersion (A) and the polyvinyl alcohol aqueous solution (A) were each diluted with ion-exchanged water to a solid content of 0.6% by mass. Then, 70 parts by mass of the diluted fine fibrous cellulose dispersion were mixed with 30 parts by mass of the diluted polyvinyl alcohol aqueous solution to obtain a mixed solution. Furthermore, the finished basis weight of the fiber sheet was 35 g / m 2 The mixture was weighed out so that the mixture had a thickness of 100 μm, and spread on a commercially available acrylic plate. A damming frame (inner dimensions 250 mm × 250 mm, height 5 cm) was placed on the acrylic plate to obtain a predetermined basis weight. The mixture was then dried in a dryer at 70°C for 24 hours and peeled off from the acrylic plate to form a fiber layer (a layer containing fine fibrous cellulose). The thickness of the fiber layer was 25 μm.
[0210] (Formation of resin layer) A resin coating liquid was obtained by mixing 8.5 parts by mass of modified polycarbonate resin (manufactured by Mitsubishi Gas Chemical Company, Iupizeta FPC-2136), 60 parts by mass of toluene, and 30 parts by mass of methyl ethyl ketone. Next, 1.5 parts by mass of an isocyanate compound (manufactured by Asahi Kasei Chemicals Corporation, Duranate TPA-100) was added as an adhesion aid to the resin coating liquid and mixed. The viscosity of the resin coating liquid measured by the measurement method described below was 30 cps. This resin coating liquid was applied to one side (the side in contact with the acrylic plate) of the fiber layer with a bar coater. Then, the resin coating liquid was cured by heating at 100°C for 1 hour to form a resin layer (first resin layer). Next, a resin layer (second resin layer) was formed on the opposite side of the fiber layer in the same manner. The thickness of the resin layer was 3 μm per side. By the above procedure, a laminated sheet in which resin layers were laminated on both sides of the fiber layer (fine fibrous cellulose-containing layer) was obtained.
[0211] <Example 2> In Example 1 (formation of the fiber layer), the mixing amount of the diluted fine fibrous cellulose dispersion (A) was changed to 40 parts by mass, and the mixing amount of the diluted aqueous polyvinyl alcohol solution was changed to 60 parts by mass, and the same procedure was followed as in Example 1 to obtain a laminated sheet.
[0212] <Example 3> In Example 1 (formation of the fiber layer), the finished basis weight of the fiber sheet was 70 g / m 2 A laminate sheet was obtained in the same manner as in Example 1, except that the thickness of the fiber layer was changed to 50 μm.
[0213] <Example 4> In Example 2 (formation of the fiber layer), the finished basis weight of the fiber sheet was 70 g / m 2 A laminate sheet was obtained in the same manner as in Example 2, except that the thickness of the fiber layer was changed to 50 μm.
[0214] <Example 5> In Example 1 (formation of the fiber layer), the finished basis weight of the fiber sheet was 140 g / m 2 A laminate sheet was obtained in the same manner as in Example 1, except that the thickness of the fiber layer was changed to 100 μm.
[0215] <Example 6> In Example 2 (formation of the fiber layer), the finished basis weight of the fiber sheet was 140 g / m 2 A laminate sheet was obtained in the same manner as in Example 2, except that the thickness of the fiber layer was changed to 100 μm.
[0216] <Example 7> In Example 6 (formation of fiber layer), the mixed amount of the diluted fine fibrous cellulose dispersion (A) was changed to 20 parts by mass, and the mixed amount of the diluted aqueous polyvinyl alcohol solution was changed to 80 parts by mass, and the same procedure was followed as in Example 6 to obtain a laminated sheet.
[0217] <Example 8> In Example 7 (formation of fiber layer), the mixed amount of the diluted fine fibrous cellulose dispersion (A) was changed to 10 parts by mass, and the mixed amount of the diluted aqueous polyvinyl alcohol solution was changed to 90 parts by mass, and the same procedure was followed as in Example 7 to obtain a laminated sheet.
[0218] <Example 9> A laminated sheet was obtained in the same manner as in Example 4 (formation of the fiber layer), except that the fine fibrous cellulose dispersion (B) was used.
[0219] <Example 10> A laminate sheet was obtained in the same manner as in Example 4 (formation of the fiber layer), except that the fine fibrous cellulose dispersion (C) was used.
[0220] <Example 11> A laminate sheet was obtained in the same manner as in Example 4 (formation of resin layer), except that the thickness of each resin layer was changed to 1 μm.
[0221] <Example 12> A laminate sheet was obtained in the same manner as in Example 4 (formation of resin layer), except that the thickness of each resin layer was changed to 4.5 μm.
[0222] <Example 13> In Example 1 (dissolution of polyvinyl alcohol), a modified polyvinyl alcohol having a hydrophilic ethylene oxide group (Gohsenx, manufactured by Mitsubishi Chemical Corporation) was used. TM The other procedures were the same as in Example 4 to obtain a laminate sheet.
[0223] <Example 14> In Example 1 (dissolution of polyvinyl alcohol), a polyvinyl alcohol aqueous solution (C) was used in which polyvinyl alcohol having a polymerization degree of 500 (Poval 105, manufactured by Kuraray Co., Ltd., saponification degree: 98 to 99 mol%) was dissolved. The other procedures were the same as in Example 4, and a laminate sheet was obtained.
[0224] <Example 15> In Example 1 (dissolution of polyvinyl alcohol), a polyvinyl alcohol aqueous solution (D) in which polyvinyl alcohol having a polymerization degree of 1,700 (Poval 117, manufactured by Kuraray Co., Ltd., saponification degree: 98 to 99 mol%) was dissolved was used. The other procedures were the same as in Example 4 to obtain a laminated sheet.
[0225] <Example 16> In Example 1 (dissolution of polyvinyl alcohol), a polyvinyl alcohol aqueous solution (E) in which polyvinyl alcohol having a polymerization degree of 1,700 (Poval 217, manufactured by Kuraray Co., Ltd., polymerization degree: 1,700, saponification degree: 87 to 89 mol%) was dissolved was used. The other procedures were the same as in Example 4 to obtain a laminated sheet.
[0226] <Example 17> In Example 3 (formation of resin layer), 100 parts by mass of an acrylic resin (manufactured by Taisei Fine Chemical Co., Ltd., Acrylit 8KX-012C) in which an acryloyl group having a hydroxyl group is graft-polymerized, 38 parts by mass of a polyisocyanate compound (manufactured by Asahi Kasei Chemicals Co., Ltd., TPA-100), and 100 parts by mass of methyl ethyl ketone were mixed to obtain a resin coating liquid. The viscosity of the resin coating liquid measured by the measurement method described below was 50 cps. The other procedures were the same as in Example 3 to obtain a laminated sheet.
[0227] <Example 18> In Example 4 (formation of resin layer), 100 parts by mass of urethane acrylic resin (manufactured by Taisei Fine Chemical Co., Ltd., Acrylit 8UA-347A) with a mass ratio of urethane unit / acrylic unit of 2 / 8 and 9.7 parts by mass of polyisocyanate compound (manufactured by Asahi Kasei Chemicals Corporation, Duranate TPA-100) were mixed to obtain a resin coating liquid. The viscosity of the resin coating liquid measured by the measurement method described below was 36 cps. The other procedures were the same as in Example 4 to obtain a laminated sheet.
[0228] <Example 19> A laminated sheet was obtained in the same manner as in Example 4 (formation of resin layer), except that a polyester resin coating liquid (Elitter UE-3320, manufactured by Unitika Ltd.) was used. The viscosity of the resin coating liquid measured by the measuring method described later was 40 cps.
[0229] <Example 20> A laminated sheet was obtained in the same manner as in Example 4, except that a fluororesin coating liquid (manufactured by Asahi Glass Co., Ltd., Cytop) was used in the (formation of resin layer) of Example 4. The viscosity of the resin coating liquid measured by the measuring method described later was 43 cps.
[0230] <Example 21> A laminate sheet was obtained in the same manner as in Example 4, except that (dissolving polyvinyl alcohol) and (forming the resin layer) in Example 4 were changed as follows.
[0231] (Dissolution of polyvinyl alcohol) Ion-exchanged water was mixed with acetoacetyl-modified polyvinyl alcohol (Gohsenex, manufactured by Mitsubishi Chemical Corporation). TM Z-300) was added to give a concentration of 12% by mass, and the mixture was stirred at 95° C. for 1 hour to dissolve. By the above procedure, an aqueous polyvinyl alcohol solution (F) was obtained.
[0232] (Formation of resin layer) A resin coating liquid was obtained by mixing 8.5 parts by mass of a modified polycarbonate resin (manufactured by Mitsubishi Gas Chemical Co., Ltd., adjusted based on Iupizeta FPC-2136) in which a low refractive index monomer was incorporated into the polymerization and the refractive index was adjusted to 1.52, 60 parts by mass of toluene, and 30 parts by mass of methyl ethyl ketone. Next, 1.5 parts by mass of an isocyanate compound (manufactured by Asahi Kasei Chemicals Co., Ltd., Duranate TPA-100) was added as an adhesion aid to the resin coating liquid and mixed. The viscosity of the resin coating liquid measured by the measurement method described below was 32 cps. This resin coating liquid was applied to one side of the fiber layer (the side in contact with the acrylic plate) with a bar coater. Then, the resin coating liquid was cured by heating at 100°C for 1 hour to form a resin layer (first resin layer). Next, a resin layer (second resin layer) was formed on the opposite side of the fiber layer in the same manner. The thickness of the resin layer was 3 μm per side.
[0233] <Example 22> A laminate sheet was obtained in the same manner as in Example 21 (formation of resin layer), except that a modified polycarbonate resin (manufactured by Mitsubishi Gas Chemical Company, Inc., adjusted based on Iupizeta FPC-2136) in which a low refractive index monomer was incorporated into the polymerization and adjusted to have a refractive index of 1.53 was used. The viscosity of the resin coating liquid measured by the measurement method described below was 34 cps.
[0234] <Example 23> A laminate sheet was obtained in the same manner as in Example 21 (formation of resin layer), except that a modified polycarbonate resin (manufactured by Mitsubishi Gas Chemical Company, Inc., adjusted based on Iupizeta FPC-2136) in which a low refractive index monomer was incorporated into the polymerization and adjusted to have a refractive index of 1.55 was used. The viscosity of the resin coating liquid measured by the measurement method described below was 32 cps.
[0235] <Example 24> A laminate sheet was obtained in the same manner as in Example 21 (formation of resin layer), except that an acrylic polymer resin coating liquid (manufactured by Aica Kogyo Co., Ltd., adjusted based on Aica Itron Z-815-4L) in which a low refractive index monomer was incorporated into the polymerization and adjusted to have a refractive index of 1.49 was used. The viscosity of the resin coating liquid measured by the measurement method described below was 37 cps.
[0236] <Example 25> A laminate sheet was obtained in the same manner as in Example 21 (formation of resin layer), except that an acrylic polymer resin coating liquid (manufactured by Aica Kogyo Co., Ltd., adjusted based on Aica Itron Z-815-4L) in which a low refractive index monomer was incorporated into the polymerization and adjusted to have a refractive index of 1.51 was used. The viscosity of the resin coating liquid measured by the measurement method described below was 35 cps.
[0237] <Example 26> A laminate sheet was obtained in the same manner as in Example 21 (formation of resin layer), except that an acrylic polymer resin coating liquid (manufactured by Aica Kogyo Co., Ltd., adjusted based on Aica Itron Z-815-4L) in which a low refractive index monomer was incorporated into the polymerization and adjusted to have a refractive index of 1.52 was used. The viscosity of the resin coating liquid measured by the measurement method described below was 38 cps.
[0238] <Example 27> A laminate sheet was obtained in the same manner as in Example 21, except that (formation of resin layer) in Example 21 was changed as follows.
[0239] (Formation of resin layer) A UV-curable acrylic resin coating solution (AICA Industrial Co., Ltd., AICA ITRON Z-773-5MLT; containing a photopolymerization initiator) was applied to one side of the fiber layer (the side in contact with the acrylic plate) using a bar coater, and then heated at 80°C for 1 minute. Furthermore, a UV conveyor device (Eye Graphics Co., Ltd., ECS-4011GX) was used to apply an integrated light dose of 150 mJ / cm2. 2 The resin coating liquid was cured by irradiating ultraviolet rays so as to form a resin layer (first resin layer). Next, a resin layer (second resin layer) was formed on the opposite side of the fiber layer in the same manner. The thickness of the resin layer was 3 μm per side. By the above procedure, a laminated sheet was obtained in which a resin layer was laminated on both sides of the fiber layer (fine fibrous cellulose-containing layer). The viscosity of the resin coating liquid measured by the measurement method described below was 36 cps.
[0240] <Example 28> A laminate sheet was obtained in the same manner as in Example 4 (formation of the fiber layer), except that the fine fibrous cellulose dispersion (D) was used.
[0241] <Comparative Example 1> In Example 3, (the formation of a resin layer) was not carried out, and a sheet having only a fiber layer was obtained.
[0242] <Comparative Example 2> In Example 4, (the formation of a resin layer) was not carried out, and a sheet having only a fiber layer was obtained.
[0243] <Comparative Example 3> A laminated sheet was obtained in the same manner as in Example 3 (formation of resin layer), except that a resin layer (second resin layer) was provided only on the surface of the fiber layer not in contact with the acrylic plate.
[0244] <Comparative Example 4> A laminated sheet was obtained in the same manner as in Example 4 (formation of resin layer), except that a resin layer was provided only on the surface of the fiber layer that was not in contact with the acrylic plate.
[0245] <Comparative Example 5> A laminate sheet was obtained in the same manner as in Example 3 (formation of resin layer), except that the thickness of the resin layer was set to 10 μm.
[0246] <Comparative Example 6> A laminate sheet was obtained in the same manner as in Example 4 (formation of resin layer), except that the thickness of the resin layer was set to 10 μm.
[0247] <Comparative Example 7> (Dissolution of polyethylene oxide) Polyethylene oxide (PEO-18, manufactured by Sumitomo Seika Chemicals Co., Ltd.) was added to ion-exchanged water to a concentration of 12 mass % and dissolved therein. By the above procedure, an aqueous solution of polyethylene oxide was obtained.
[0248] (Formation of fiber layer) The fine fibrous cellulose dispersion (A) and the polyethylene oxide aqueous solution were each diluted with ion-exchanged water to a solid content concentration of 0.6% by mass. Then, 83 parts by mass of the diluted fine fibrous cellulose dispersion were mixed with 17 parts by mass of the diluted polyethylene oxide aqueous solution to obtain a mixed solution. Furthermore, the finished basis weight of the fiber sheet was 50 g / m 2 The mixture was weighed out so that the mixture had a thickness of 100 μm, and spread on a commercially available acrylic plate. A damming frame (inner dimensions 250 mm × 250 mm, height 5 cm) was placed on the acrylic plate to obtain a predetermined basis weight. The mixture was then dried in a dryer at 70°C for 24 hours and peeled off from the acrylic plate to form a fiber layer. The thickness of the fiber layer was 33 μm.
[0249] (Formation of resin layer) 15 parts by mass of modified polycarbonate resin (manufactured by Mitsubishi Gas Chemical Company, Iupizeta FPC-2136), 57 parts by mass of toluene, and 28 parts by mass of methyl ethyl ketone were mixed to obtain a resin coating liquid. Next, 2.25 parts by mass of an isocyanate compound (manufactured by Asahi Kasei Chemicals Corporation, Duranate TPA-100) was added as an adhesion aid to the resin coating liquid and mixed. The viscosity of the resin coating liquid measured by the measurement method described below was 40 cps. This resin coating liquid was applied to one side of the fiber layer with a bar coater. Then, the resin coating liquid was cured by heating at 100 ° C for 1 hour to form a resin layer. Next, a resin layer was formed on the opposite side of the fiber layer in the same manner. The thickness of the resin layer was 3 μm. By the above procedure, a laminated sheet in which resin layers were laminated on both sides of the fiber layer (fine fibrous cellulose-containing layer) was obtained.
[0250] <Measurement> (Thickness of resin layer) A cross section of the sheet was cut out using an ultramicrotome UC-7 (manufactured by JEOL, UC-7), and the cross section was observed with an electron microscope, a magnifying glass or visually, and the measured value was taken as the thickness of the resin layer.
[0251] (Viscosity of resin coating liquid) The viscosity of the prepared resin coating liquid was measured using a Brookfield viscometer (analog viscometer T-LVT, manufactured by BLOOKFIELD Corp.) The measurement conditions were a rotation speed of 60 rpm, and the viscosity value 1 minute after the start of measurement was recorded as the viscosity of the resin coating liquid.
[0252] <Evaluation> (Adhesion) Compliant with JIS K 5400:1990, 1mm on the resin layer surface 2 Then, cellophane tape (manufactured by Nichiban Co., Ltd.) was applied on top of the 100 pieces of cross-cut, and 1.5 kg / cm 2 The sheet was pressed against the sheet with a load of 0.01 mm. The cellophane tape was then peeled off in a 90° direction. The adhesion between the fiber layer (fine fibrous cellulose-containing layer) and the resin layer was evaluated according to the following criteria based on the number of peeled squares. Note that the evaluation sheets of Comparative Examples 1 and 2 were not evaluated because they did not have a resin layer. A: The number of peeled squares is 0 points B: The number of peeled squares is 1 or more but less than 5 C: The number of peeled squares is 5 or more but less than 10 D: The number of peeled squares is 10 or more.
[0253] (water resistance) In accordance with JIS R 3257:1999, a dynamic water contact angle tester (1100DAT, manufactured by Fibro Corporation) was used to drop 4 μL of ion-exchanged water onto both surfaces of the laminate sheet, and the water contact angle after 30 seconds was measured. A: The contact angle on both sides of the laminated sheet is 80° or more. B: The contact angle on both sides of the laminate sheet is 75° or more and less than 80°, or the contact angle on at least one side of the laminate sheet is 75° or more and less than 80°, and the contact angle on the other side of the laminate sheet is 80° or more. C: The contact angle of at least one surface of the laminated sheet is less than 75°.
[0254] (Refractive Index) The refractive index of the fiber layer before lamination was measured using an Abbe refractometer (NAR-3T, manufactured by ATAGO Co., Ltd.) in accordance with JIS K 7142:2008. When measuring the refractive index of the resin layer, 0.5 mL of the resin coating liquid was applied onto a glass substrate (2 cm x 2 cm) for Abbe measurement, and heated at 100°C for 1 hour to obtain a resin layer. The resin layer formed on the glass substrate was used for measuring the refractive index as it was, without being peeled off from the glass substrate.
[0255] (Surface roughness) The surface roughness of both sides of the laminated sheet was evaluated using an optical interference type non-contact surface profile measuring instrument (Ryoka Systems Co., Ltd., non-contact surface / layer cross-sectional profile measuring system VertScan2.0, R5500GML) in accordance with JIS B 0601:1994. The surface roughness was calculated using a ×10 objective lens with a measurement range of 470 μm × 350 μm.
[0256] (transparency) The haze of the laminated sheet was evaluated using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory Co., Ltd.) in accordance with JIS K 7136: 2000. The transparency was also evaluated according to the following criteria based on the haze value. A: Haze is less than 0.5% B: Haze is 0.5% or more but less than 1% C: Haze is 1% or more
[0257] (tensile modulus) The tensile modulus of the laminated sheet was measured using a tensile tester Tensilon (manufactured by A&D Co., Ltd.) in accordance with JIS P 8113:2006. The modulus of elasticity was calculated from the maximum positive slope of the SS curve. When measuring the tensile modulus of elasticity, the specimen was conditioned at 23°C and 50% relative humidity for 24 hours.
[0258] (Moisture percentage) The laminated sheet was cut into test pieces measuring 5 cm x 5 cm, and the test pieces were conditioned at 23°C and 50% relative humidity for 24 hours, and then dried in a thermostatic oven at 105°C until completely dry. The weights of the test pieces before and after drying were measured, and the moisture content of the laminated sheet was calculated using the following formula. Moisture content of laminated sheet (mass%) = (WD) / W x 100 Here, W is the weight (g) of the test piece after humidity conditioning, and D is the weight (g) of the test piece after bone drying.
[0259] [Table 1]
[0260] [Table 2]
[0261] [Table 3]
[0262] [Table 4]
[0263] The sheets (laminate sheets) obtained in the examples had high transparency. The sheets (laminate sheets) obtained in the examples also had excellent water resistance. On the other hand, the sheets obtained in the comparative examples had poor transparency.
[0264] Furthermore, particularly in Examples 21 to 27, the appearance of the obtained sheets (laminate sheets) tended to be such that the occurrence of ripples (rainbow unevenness) due to optical interference was suppressed. [Explanation of symbols]
[0265] 2 Fiber layer 6 Resin layer 10 Sheets
Claims
1. A sheet having a fiber layer and a resin layer on both sides of the fiber layer, The fiber layer contains fibrous cellulose having a fiber width of 1000 nm or less, The sheet has a surface roughness (Ra) of 8.3 nm or less on both sides.
2. The sheet according to claim 1 , wherein each of the resin layers has a thickness of 10 μm or less.
3. 3. The sheet of claim 1 or 2, wherein the fibrous cellulose has ionic substituents.
4. The sheet according to claim 3 , wherein the ionic substituent is a phosphorus oxoacid group or a substituent derived from a phosphorus oxoacid group.
5. The sheet according to any one of claims 1 to 4, wherein the refractive index of the fiber layer is 1.51 to 1.
60.
6. The sheet according to any one of claims 1 to 5, wherein the fibrous layer further comprises a hydrophilic polymer.
7. The sheet according to claim 6 , wherein the hydrophilic polymer is polyvinyl alcohol.
8. The sheet according to claim 7, wherein the polyvinyl alcohol has a degree of saponification of 99.9% or less.
9. The sheet according to any one of claims 1 to 8, wherein the resin layer contains an amorphous resin.
10. The sheet according to any one of claims 1 to 9, wherein the resin layer is a solvent-coated layer.
11. The sheet according to any one of claims 1 to 10, wherein the fiber layer has a thickness of 10 to 1000 µm.
12. The sheet according to any one of claims 1 to 11, wherein the resin layer contains an isocyanate compound.
13. The sheet according to any one of claims 1 to 12, having a haze value of less than 0.5%.
14. The sheet according to any one of claims 1 to 13, having a moisture content of 12% by mass or less.
15. The sheet according to any one of claims 1 to 14, having a tensile modulus of elasticity of 2.5 GPa or more at 23°C and a relative humidity of 50%.
16. The sheet according to any one of claims 1 to 15, which is for an optical member.
17. The sheet according to any one of claims 1 to 16, wherein the refractive index ratio between the fiber layer and the resin layer calculated by the following formula is 0.98 or more and 1.02 or less. Refractive index ratio = refractive index of fiber layer / refractive index of resin layer
18. The sheet according to any one of claims 1 to 17, wherein the refractive index of the fiber layer is from 1.51 to 1.
54.
19. A method for producing a sheet, comprising a step of forming a resin layer on both sides of a fiber layer containing fibrous cellulose having a fiber width of 1000 nm or less, The method for producing a sheet, wherein the surface roughness (Ra) of both surfaces of the sheet is 8.3 nm or less.
20. The method for producing a sheet according to claim 19 , wherein the resin layer has a thickness of 10 μm or less.
21. the step of forming the resin layer is a step of applying a resin coating liquid to both surfaces of the fiber layer to form a resin layer, The resin coating liquid contains a solvent, The method for producing a sheet according to claim 19 or 20, wherein the viscosity of the resin coating liquid is 100 cps or less.
22. The method for producing a sheet according to claim 21 , wherein the resin coating liquid has a solid content of 12% by mass or less.
Citation Information
Patent Citations
Polycarbonate resin / cellulose fiber laminate and method for producing the same
JP2010023275A
Method for producing fine-fibrous cellulose composite sheet-laminated form
JP2011149124A
Gas barrier laminate and method of producing the same
JP2014223737A
Laminate, and production method of laminate
JP2017128033A
Laminate
JP2018069600A